Source rock evaluation of the Upper Cretaceous black shales in the Abu Tartur Plateau: implications for untapped hydrocarbon resources in south Western Desert, Egypt - Ahmed El Shawaf; Mahmoud Leila; Waleed Sh El Diasty; Ghaleb Issa; Ahmed Khairy; Christopher Vane; Tarek Anan (Journal of African Earth Sciences, 2027)

The first description of CTNNB1 syndrome in the Tunisian population: clinical investigation, molecular docking and molecular dynamics simulation of β-catenin/E-cadherin complex - Marwa Kharrat; Wafa bouchaala; Magdy M. D. Mohammed; Abir ben issa; Faiza Fakhfakh; Fatma kamoun; Chahnez Triki (Molecular Biology Reports, 2026)

AI-Assisted Simulation and Design of Sustained Release Metformin Tablets: Experimental Validation and Predictive Accuracy Assessment - Muthanna Abdulkarim; Abdullah B. Alabdulwahab; Arwa Alhaj Issa; Gamal M. Mahrous; Adel F. Alghaith; Sally Almanasra; Khaled Suwais (Journal of Pharmaceutical Innovation, 2026)

Hydrodynamic connectivity and potential oil pollution exposure of Marine Protected Areas: Implications for coastal management in Senegal - Issa Ba; Bruno Blanke; Siny Ndoye; Bamol Ali Sow; Patrice Bellec; Martial Boutet; Birane Ndom (Ocean & Coastal Management, 2026)

Readiness for Data-Driven Decision Making and Response to Intervention among School Counseling and Awareness Specialists in the Sultanate of Oman - Amal Alhadabi; Said Aldhafri; Hasna Alhindasi; Fahima Alsaidi; Siham Alshaaibi; Issa Alhidfi; Sultan Alyahyai (Next Research, 2026)

Cross-sectional facies model for the Cambro–Ordovician and Upper Cretaceous mixed siliciclastic-carbonate reservoirs in the central eastern Sirte Basin, Libya: Porosity and permeability estimation - Muneer Abdalla; Abdalla Abdelnabi; Ahmad Issa; Abdlsaid Ibrahem; Saleh Qaysi (Journal of African Earth Sciences, 2026)

Comparative efficacy of commercial infectious bursal disease vaccination strategies against emerging novel variant IBDV (Genotype A2d) - Kamal Samy Ahmed Mohamed Issa; Hany Fawzy Ellakany; Ahmed Ramadan Gado; Shady Hesham Elrayes; Ismail Ismail Abughanima; Ahmed R. Elbestawy; Rania F. El Naggar; Ahmed H. Salaheldin; Mohammed A. Abdelsabour; Hatem S. Abd El-Hamid; Mohammed A. Rohaim (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Design of an Interactive Agricultural Injury Dashboard: Enhancing Data Visualization and Stakeholder Engagement Using AgInjuryNews Data - Sihan Li; Michael Twidale; Jodi Schneider; Serap Gorucu; Paul Davidson; Bryan Weichelt; Salah Issa (Journal of Agromedicine, 2026)

Cervical artery dissection after upper respiratory infection: clinical features and prognosis - Sara D. B. Rosa; Mafalda Soares; Ana Paiva Nunes; Liqi Shu; Eileen Wu; Nils Henninger; Jayachandra Muppa; Mirjam R. Heldner; Kateryna Antonenko; Setareh Omran; Ahmad Nehme; Aaron Rothstein; et al. (Acta Neurologica Belgica, 2026)

Microplastics and nanoplastics from food packages: linking contamination and exposure to potential health impacts and mitigation strategies - Joachim Dotto Matondo; Abdulsudi Issa-Zacharia; James Simon Chacha (Trends in Food Science & Technology, 2026)

The geomorphology of the mature, fluviokarst-dominated Mesijune salt extrusion (Zagros Mountains, Iran). Insights into the evolution of salt fountains - Francisco Gutiérrez; Issa Ilyati; Guillermo Pérez-Villar (Geomorphology, 2026)

A mycelium-associated Pseudomonas strain from Pythium aphanidermatum, deleterious to tomato plants, and exhibiting metalaxyl degradation potential - Khulood Khalid Al-Ruqashi; Fatma Al-Makhmari; Waad Al-Harthi; Ahmed Al-Ghafri; Issa Hashil Al-Mahmooli; Jamal Al-Sabahi; Daniel Menezes-Blackburn; Abdullah Mohammed Al-Sadi; Rethinasamy Velazhahan (Australasian Plant Pathology, 2026)

Neurological manifestations in a cat with tick-borne relapsing fever caused by Borrelia persica - Dor Shwartz; Abir Issa; Yaarit Nachum-Biala; Gad Baneth (Research in Veterinary Science, 2026)

Climate-responsive envelope design for educational buildings: A comparative simulation study between the UK and Egypt - Bertug Ozarisoy; Mubarak Elnour Ismail; Issa Chaer; Rania Rushdy Moussa; Mahmoud Alghrieb; Engy Elshazly; Iman El-Mahallawi; Hesham Safwat; Ahmad I. Elshamy (Energy and Buildings, 2026)

Serum 25-hydroxyvitamin D and neurological disability in multiple sclerosis: a cross-sectional study in a Libyan multicenter cohort - Osamah Alrouwab; Hayet Benhizia; Issa Amara (Acta Neurologica Belgica, 2026)

A cost-efficient internal standard approach for busulfan quantification: MS-based investigation of adduct formation in therapeutic drug monitoring - Erfan Jahan Mehmani; Niloofar Rastegarpanah; Issa Zarei; Massoud Amanlou (DARU Journal of Pharmaceutical Sciences, 2026)

Intraseasonal modulation of sea surface temperatures in the Tropical North Atlantic by African Easterly Waves - Marc Kakante Mendy; Florent Gasparin; Manon Gévaudan; Moussa Diakhaté; Issa Sakho; Julien Jouanno (Ocean Science, 2026)
The sea surface temperature (SST) variability in the Tropical North Atlantic (TNA) plays a crucial role in the regional climate by modulating the Intertropical Convergence Zone (ITCZ) and influencing precipitation, convective systems, and tropical cyclones. While atmospheric synoptic-scale intraseasonal variability in this region is dominated by African Easterly Waves (AEWs), their impact on SST remains poorly understood. This study investigates the modulation of SST by AEWs using a regional configuration of a coupled ocean-atmosphere model and moored surface buoy air-sea observations. The results reveal a significant AEWs signature in SST anomalies, with typical temperature fluctuations of approximately ±0.3 °C (reaching up to ±0.5 °C for the strongest events). A heat budget analysis shows that AEWs mainly influence SST through modulation of the latent heat flux, shortwave radiation, and vertical mixing. The contribution of ocean mixing and that of the air-sea fluxes appear to be of similar order. The dominant 3–5 d AEWs exhibit a stronger impact than their 6–9 d counterparts. These findings highlight the role of AEWs in driving SST variability and mixed-layer dynamics, underscore the importance of accurately representing them in coupled climate models, and call for further investigation into their influence on the mean and seasonal upper-ocean state.

Blue carbon stocks, accumulation rates and knowledge gaps in Africa - Janine B. Adams; Paula Pattrick; Pere Masqué; Dennis Adotey; Elsheikh Bashir Ali; Abdelgadir Bashir Mohamed Awatif; Mohamed Fathi Ben Hamouda; Moncef Benmansour; Joseph F. Charles; Jerome Harlay; Lucienne Human; Linet Kiteresi Imbayi; et al. (Ocean & Coastal Management, 2026)

Unmasking a feminizing adrenocortical carcinoma: A case report and literature review on diagnostic delay in a young male with persistent fever of unknown origin - Mohammed Amer Kamel; Hamid Ghanem; Nizar Abu Hamdeh; Hala Hamad; Tamer Issa Adawi; Sami Bannoura; Haitham Abu Khadija; Mohammad Alnees (Next Research, 2026)

Hybrid GO-MXene nanofluids in 3D oscillating heat pipes for efficient urban PV cooling: Improved energy, exergy, and economic performance - Mahyar Kargaran; Saeed Zeinali Heris; Hamid Reza Goshayeshi; Seyed Borhan Mousavi; Issa Chaer (Energy and Buildings, 2026)

The Structural and Surface Properties of Laboratory-Synthesized ZnO Nanomaterials Determine Their Dissolution, Leaching, and Bioavailability in Different Soils - Marina de-Francisco; Andreia Romeiro; Luisa Durães; Silvia Álvarez-Torrellas; Amir Alejandro Subhi-Issa; Patricia Almendros (Journal of Soil Science and Plant Nutrition, 2026)
Although ZnO nanoparticles (ZnO-NPs) are promising controlled-release Zn sources, the influence of synthesis route and precursor chemistry on Zn dissolution, leaching, and bioavailability in different soils remains unclear. This study compared five laboratory-synthesised ZnO formulations to determine how formulation design affects Zn mobility and availability in sand and soils. ZnO-NPs (C-NIT-1, C-SUL, C-NIT-2, S-ACE, and S-SUL) were synthesised via co-precipitation or sol–gel routes using different precursors and hydroxide sources, yielding distinct physicochemical properties. Dissolution was assessed in aqueous media, and leaching was evaluated through column experiments with sand, acidic soil (pH 5.8), and calcareous soil (pH 8.3). Zinc in leachates was periodically quantified, and bioavailable Zn was determined using low-molecular-weight organic acids. The formulations showed marked differences in structural and surface properties, with hydrodynamic diameters of 183–603 nm and zeta potentials from − 7.4 to + 16.5 mV. SEM revealed variable aggregation, with C-NIT-2 forming aggregates up to 10 μm. Elemental analysis confirmed precursor-dependent variation in S and Zn contents. These differences resulted in contrasting Zn release patterns: in sand, C-SUL and S-ACE released Zn rapidly, whereas C-NIT-1 and S-SUL showed slower kinetics. In acidic soil, C-SUL leached 1.4 mg Zn (> 80% of available Zn), while in calcareous soil total leaching remained below 0.2 mg. Overall, the results demonstrated that Zn release and mobility are not determined solely by particle size, but by the combined influence of other key parameters, such as porosity, surface charge, solubility, synthesis conditions, as well as soil properties.

Correction to: Comprehensive tsunami hazard assessment for Wudam As-Sahil, Northern Oman: Integrating deterministic and probabilistic approaches - Issa El-Hussain; Zaid Al-Habsi; Rachid Omira; Ahmed Deif; Adel Mohamed; Maria Ana Baptista; Yousuf Al-Shijbi (Arabian Journal of Geosciences, 2026)

Melt-Extruded Paclitaxel Nanocrystal-Loaded Sutures for Sustained Local Drug Delivery - Hala M. Abdelhakk; Alhassan Issa; Crystal S. Shin; Feng Zhang (Pharmaceutical Research, 2026)

HydrocamCompute: Serverless computing workflow for camera-based hydrological monitoring - Sajan Neupane; Jeffery S. Horsburgh; Razin Bin Issa; Sierra Young (Environmental Modelling & Software, 2026)

Modeling seismic risk and economic loss for urban sustainability: insights from a Gulf city - Abdullah Ansari; Issa El-Hussain; Yousuf Al-Shijbi; Ayed E. Alluqmani; Hajar Al-Qayoudhi; Yewuhalashet Fissha; Shima Albalushi; Badee Alshameri (Modeling Earth Systems and Environment, 2026)
This study delivers the first comprehensive microzonation-based seismic risk assessment for the Al-Seeb region in Muscat, Oman. It integrates geotechnical, structural, environmental, and socio-economic vulnerability factors using a Geographical Information System (GIS) based multi-criteria framework. The Analytic Hierarchy Process (AHP) was employed to systematically weight and integrate these indicators, ensuring an objective evaluation of their relative influence on overall seismic vulnerability. Moving beyond traditional methods, it translates microzonation data into spatially distributed Average Annual Loss (AAL) zones and estimates economic impacts through Loss Exceedance Curves (LEC) and Probable Maximum Loss (PML). By coupling detailed hazard zonation with building typologies and infrastructure exposure, the study develops an asset-level risk profile, revealing sharp spatial variations in seismic risk driven by site conditions and construction quality. The results serve as a vital planning tool for civil authorities, aligning with Oman Vision 2040 and United Nations Sustainable Development Goal (UN SDG) 11. The approach offers a scalable model for rapidly urbanizing Gulf cities such as Doha, Riyadh, Dubai, and Kuwait, providing a data-informed foundation for enhancing infrastructure resilience and strengthening disaster risk management strategies.

Co-circulation of viral and bacterial diseases in the field: insights from symptom observation and detection of two rice pathogens - Estelle Billard; Martine Bangratz; Abalo Itolou Kassankogno; Phonsiri Saengram; Abdoul Kader Guigma; Olivier Cotto; Gaël Thébaud; Issa Wonni; Drissa Sérémé; Nils Poulicard; Sebastien Cunnac; Mathilde Hutin; et al. (European Journal of Plant Pathology, 2026)

Effects of rock fragments on water infiltration and physical properties of volcanic soils in southern Brazil - Geane Alves de Moura; Fabrício de Araújo Pedron; Paulo Ivonir Gubiani; Ricardo Simão Diniz Dalmolin; Jean Michel Moura-Bueno; Luis Eduardo Akiyoshi Sanches Suzuki; Noeme da Costa Santos; Raí Ferreira Batista; Issa Buana Alfane; Luís Felipe Rech; Victor Hugo Carvalho Sabóia; Bruna Trevizan Paese; et al. (Geoderma Regional, 2026)

The role of osmotic pressure drop in enhancing the predictive performance of dynamic models for sustainable forward osmosis water desalination - Jaouad Eddouibi; Imane Chaoui; Issa Ndiaye; Souad Abderafi; Sébastien Vaudreuil; Meriem Chaanaoui; Tijani Bounahmidi (Environmental Science and Pollution Research, 2026)

Reported food adulteration in the MENA region (2019–2024): A multilingual media and RASFF analysis of trends, hazard types and regulatory gaps - Christelle Bou-Mitri; Alain Martinos; Darine Mahmoud; Aline Issa; Jacqueline Doumit; Hussein F. Hassan (Food Bioscience, 2026)

Staphylococcus lugdunensis infective endocarditis: a multicentre international observational study - Benjamin Lefevre; Gilbert Habib; Bruno Hoen; Christine Selton-Suty; Mary Philip; Nahema Issa; Pierre Danneels; Marine De La Chapelle; Colin Deschanvres; Marie-Line Erpelding; Pierre Tattevin; Audrey Le Bot; et al. (Infectious Diseases, 2026)

Urban balcony gardens: exploring a resident-led nature-based solution - Salma N. Talhouk; Carine Ghassibe; Samar Morkos; Dany Abou Jaoude; Ibrahim Issa (Urban Ecosystems, 2026)

A review of the role of drinking water as a potential reservoir for the spread of antibiotic-resistant bacteria in Nigeria - Akeem Ganiyu Rabiu; Abimbola Olumide Adekanmbi; Abidemi Joseph Marcus; Sheriffdeen Issa Bale; Morufat Oluwatosin Olaitan; Odunsanmi Ajibodun Waleola; Abdulakeem Miftahudeen Ogunlana; Saheed Abiodun Ayoola; Fatimah Adenike Ajadi; Olutayo Israel Falodun (Environmental Monitoring and Assessment, 2026)

Does artificial intelligence reduce carbon emissions in OECD and BRICS? Examining the role of research and development - Issa Hamadou; Teguh Yudo Wicaksono; M. Luthfi Hamidi (Journal of Environmental Management, 2026)

HydrocamCollect: A robust data acquisition and cloud data transfer workflow for camera-based hydrological monitoring - Sajan Neupane; Jeffery S. Horsburgh; Razin Bin Issa; Sierra Young (Environmental Modelling & Software, 2026)

A multidisciplinary approach for flash flood management in Wadi systems: insights from geoinformatics and 2D-electrical resistivity tomography - Abdelhalim Ali; Mohamed Attwa; Mohamed El-Bastawesy; Mamoun Ahmed; Mona Kaiser; Ahmed Gad; Khaled Mamoun; Ala Ahmed; Salem Issa; Khalid Al Bloushi (Natural Hazards, 2026)

Characterization and Assessment of Iron-Reducing Capacity of Cultivable Bacteria from Iron-Toxic Rice Soils in Burkina Faso - Cécile H. Otoidobiga; Wendlassida P. Ouédraogo; Adama Sawadogo; Ernest Somé; Kévin S. Bationo; Massiribi B. Barro; Susumu Asakawa; Dayeri Dianou; Issa Wonni; Ynoussa Maïga; Aboubakar S. Ouattara; Alfred S. Traoré (Current Microbiology, 2026)

The possible role of lycopene on the cerebellum of albino rat prenatally exposed to valproic acid: Animal model of autism spectrum disorder - Lubna T. Eid; Mostafa M. El-Habeby; Noha M. Issa; Nermeen M. Nooreldien (Tissue and Cell, 2025)

Metformin-loaded Chitosan nanoparticles alleviate insulin resistance in the polycystic ovarian syndrome rat model through modulation of PI3K/AKT/ GLUT4 in ovarian tissue - Samah Magdy Issa; Eman H. Thabet; Abeer.E. Dief; Walaa Omar; Samar R. Saleh; Marwa M. Essawy; Eman El Eter (Reproductive Biology, 2025)

From mineral to sensing: Colorimetric determination of ciprofloxacin from water and food samples using natural chalcopyrite as nanozyme - Issa Haruna Nkuruma; Nenguba Poloko; Asfawossen Asrat; Andrew E.H. Wheatley; Pogisego Dinake; Melisew Tadele Alula (Food Chemistry, 2025)

Metabolomic approach to explore the chemical composition and health benefits of macroalgae: A comprehensive study of Palmaria palmata, Ascophyllum nodosum, and Chondrus crispus - Natália Čmiková; Milena D. Vukić; Nenad L. Vukovic; Jaroslav Havlík; Hanán Issa-Issa; Ángel A. Carbonell-Barrachina; Ivona Jančo; Vittorio Vinciguerra; Stefania Garzoli; Miroslava Kačániová (Food Chemistry, 2025)

Is mechanized conservation agriculture a promising solution for smallholder farmers? Evaluating its short-term agronomic and economic performance in Ethiopia - Bisrat G. Awoke; Thomas Daum; Karlheinz Köller; Dereje A. Anawte; Mubarek M. Issa; Teshome B. Gutema; Debele D. Enki; Godfrey Omulo; Regina Birner (Field Crops Research, 2025)

Evaluating the impact of different agropastoral practices on wind erosion in western Sahel - Paul-Alain Raynal; Jean-Louis Rajot; Beatrice Marticorena; Abdourahmane Tall; Baptiste Lemaire; Jean-Alain Civil; Diouma Cor Fall; Gualbert Seraphin Dorego; Ibrahima Sarr; Issa Faye; Ambre Emmendoerffer; Henri Guillaume; et al. (CATENA, 2025)

Enhancing the biomass and the nutritional value of Hermetia illucens by rearing on biotreated agricultural and bird wastes - AbdelfattahA. Khalaf; Karam T.H. Issa; Heba H.R. Ahmed; Ashraf S.A. El-Sayed (Biomass and Bioenergy, 2025)

Elucidating Heavy Metals Ions Detection Using Screen Printed Electrodes with Starch Carbon Dots as Modifier - Sathya Rau Subramaniam; Zurina Zainal Abidin; Mohammed Abdullah Issa; Nur Haninah Harun; Musa Yahaya Pudza (Water, Air, & Soil Pollution, 2025)

End-to-end deep SAE-DNN model for predicting Egyptian buffalo calf sex, weight, and daily milk yield - Sali Issa; Montaser Elsayed Ali; Qi Wang; Fatimah A. Al-Saeed; Mohamed Abdelrahman (Tropical Animal Health and Production, 2025)

Antifungal Potential of Nostoc Commune Extract against Saprolegnia Australis - Arash Azari; Pedram Zahedi Mohammadi; Maryam Gholizadeh; Issa Gholampour Azizi; Ehsan Nazifi (Thalassas: An International Journal of Marine Sciences, 2025)

Bacillus subtilis isolates from yoghurt suppress gray mold disease caused by Botrytis cinerea on postharvest strawberry fruit - Sara Al-Hatmi; Abdullah Mohammed Al-Sadi; Fatma Said Al-Mashani; Issa Hashil Al-Mahmooli; Mohamed Abdullah Al-Kindi; Rethinasamy Velazhahan (Journal of Plant Pathology, 2025)

Bridging the divide: How unequal carbon dioxide removal deployment threatens climate equity and global mitigation feasibility - Raphael Apeaning; Puneet Kamboj; Mohamad Issa Hejazi (Sustainable Production and Consumption, 2025)

Diapiric and tectonic geomorphology of the river-damming Jahani salt extrusion associated with the strike-slip Kareh Bas Fault, including DInSAR displacement data (Zagros Mountains, Iran) - Francisco Gutiérrez; Mahmud Haghshenas Haghighi; Issa Ilyati; Mahdi Motagh; Miren del Val (Geomorphology, 2025)

KI-gestütztes Videomonitoring aquatischer Ökosysteme - Chancen, Grenzen und Praxisanforderungen - Jeffrey A. Tuhtan; Bernd Mockenhaupt; Frederic de Schaetzen; Rodrigo W. Issa; Adrien Bertaud; Damien Sidler; Henning Müller; Christian Haas (WASSERWIRTSCHAFT, 2025)

Development of an analytical model for assessing the adsorptive properties of traditional medicinal formulations from Burkina Faso in relation to snake venom proteins - Moumouni Bande; Cédric Delporte; Abdoul Karim Sakira; Axelle Bourez; Virginie Imbault; Xavier Bisteau; Charles Sombie; Touridomon Issa Some; Pierre Van Antwerpen (Toxicon, 2025)

Rational design of groundwater treatment sludge into visible-light-driven photocatalyst with carbon nitride - Kingsley Igenepo John; Touma B. Issa; Aleksandar N. Nikoloski; Goen Ho; Dan Li (Journal of Environmental Management, 2025)

Transition to clean fuels and technologies for cooking in developing countries: Does women representation in parliament matter? - Issa Dianda; Djakaria Tou; Martin Sawadogo (Energy Policy, 2025)

circRNA/TLR interaction: key players in immune regulation and autoimmune diseases - Chou-Yi Hsu; Alaa Khalaf Bediwi; Ahmed Hussein Zwamel; Subasini Uthirapathy; Suhas Ballal; Abhayveer Singh; Girish Chandra Sharma; Anita Devi; Sami G. Almalki; Issa Mohammed Kadhim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Narrowing the urban-rural electricity gap in Sub-Saharan Africa: Does equal distribution of political power matter? - Issa Dianda; Djakaria Tou; Patrice Rélouendé Zidouemba (The Electricity Journal, 2025)

Surface karst geomorphology in the Jahani salt extrusion, Zagros Mountains, Iran - Francisco Gutiérrez; Issa Ilyati; Mehdi Zarei (Geomorphology, 2025)

Pantoea dispersa from olive pomace compost suppresses Pythium aphanidermatum damping-off in Cucumis sativus - Ikhlass Al-Shaqsi; Yahya Al-Fahdi; Issa Hashil Al-Mahmooli; Ibrahim Al-Khusaibi; Ahmed Al-Fahdi; Abdullah Mohammed Al-Sadi; Rethinasamy Velazhahan (Indian Phytopathology, 2025)

Community perception and stewardship of public coastal infrastructure in Cedar Key, Florida - Jiayang Li; Amer Hamad Issa Abukhalaf; Eban Bean; Carla Brisotto; Mark W. Clark; Jason Von Meding; Andrea Otalora; Savanna Barry (Frontiers in Marine Science, 2025)
This study contributes to empirical evidence about how local communities may perceive and steward nature-based coastal infrastructure developed in the public realm to enhance coastal resilience. Coastal communities increasingly face flood risks driven by chronic erosion, habitat degradation, and climate change. Nature-based coastal infrastructure-such as living shorelines-offers promise for hazard mitigation, resilience, and co-benefits. However, public awareness and acceptance remain barriers to broader adoption, and little is known about perception of community-level coastal infrastructure beyond private settings. This study used an intercept survey (N = 155) in Cedar Key, Florida, U.S., to investigate public perceptions of various coastal infrastructure options across the green-gray spectrum, community stewardship of coastal infrastructure in terms of funding and maintenance, and potential factors that predict more positive perceptions of nature-based options and stronger lay stewardship. Among the five types of coastal infrastructure that we examined (i.e., vegetation-only, sills, beach nourishment, revetment, and sea wall), participants rated nature-based options (vegetation-only and sills) significantly higher for beauty. However, contrary to existing literature, we found no significant differences in perceived protection between nature-based and hardened options. Instead, beauty and protection ratings were strongly correlated for all options except sea walls. More favorable views of nature-based options were associated recognizing shoreline’s role in pollutant capture and having more pro-environmental attitudes. Findings also suggest that sills were seen as more effective than vegetation-only for erosion control and protection. Additionally, over 45% of self identified residents reported feeling responsible for maintaining coastal infrastructure significantly more than non-residents-while over 40% of tourists indicated responsibility for funding-significantly more than non-visitors. Shore-based anglers also emerged as promising stewards, expressing support for both funding and maintenance. These findings contribute to understanding public perception and potential stewardship of nature-based coastal infrastructure at the local level and inform designs that can gain stronger community preference and support.

Adapting East and Southern Africa’s livestock to climate change: a decision making under deep uncertainty-based approach for effective actions - Issa Awal Mohamed; Michiel Schaeffer; Florent Baarsch (Climate and Development, 2025)

Generation & mitigation of cyanides: A steel industrial perspective - Santanu Sarkar; Tamal Kanti Ghosh; Pratik Swarup Dash; Mahaad Issa Shammas; Sudip Chakarborty (Groundwater for Sustainable Development, 2025)

Systemic isosporosis in three species of passerine birds - Camila Issa Amaral; Ayisa Rodrigues de Oliveira; Eric Santos Oliveira; Marcelo Coelho Lopes; Maira dos Santos Carneiro Lacerda; Marcelo Pires Nogueira de Carvalho; Roselene Ecco (Veterinary Research Communications, 2025)

Clinical and pathological characterization of a feline intestinal large granular lymphocyte lymphoma (LGLL) - Camila Issa Amaral; Lorena Santos Bezerra; Acácia Eduarda de Jesus Nascimento; Nayara Toledo da Silva; Lize Amanda Basaglia Borges; Paloma Helena Sanches da Silva; Letícia Monteiro Barbosa; Anelise Carvalho Nepomuceno; Rodrigo dos Santos Horta; Geovanni Dantas Cassali; Ayisa Rodrigues Oliveira (Veterinary Research Communications, 2025)

Enhancing Ship Propulsion Efficiency Predictions with Integrated Physics and Machine Learning - Hamid Reza Soltani Motlagh; Seyed Behbood Issa-Zadeh; Md Redzuan Zoolfakar; Claudia Lizette Garay-Rondero (Journal of Marine Science and Engineering, 2025)
This research develops a dual physics-based machine learning system to forecast fuel consumption and CO2 emissions for a 100 m oil tanker across six operational scenarios: Original, Paint, Advanced Propeller, Fin, Bulbous Bow, and Combined. The combination of hydrodynamic calculations with Monte Carlo simulations provides a solid foundation for training machine learning models, particularly in cases where dataset restrictions are present. The XGBoost model demonstrated superior performance compared to Support Vector Regression, Gaussian Process Regression, Random Forest, and Shallow Neural Network models, achieving near-zero prediction errors that closely matched physics-based calculations. The physics-based analysis demonstrated that the Combined scenario, which combines hull coatings with bulbous bow modifications, produced the largest fuel consumption reduction (5.37% at 15 knots), followed by the Advanced Propeller scenario. The results demonstrate that user inputs (e.g., engine power: 870 kW, speed: 12.7 knots) match the Advanced Propeller scenario, followed by Paint, which indicates that advanced propellers or hull coatings would optimize efficiency. The obtained insights help ship operators modify their operational parameters and designers select essential modifications for sustainable operations. The model maintains its strength at low speeds, where fuel consumption is minimal, making it applicable to other oil tankers. The hybrid approach provides a new tool for maritime efficiency analysis, yielding interpretable results that support International Maritime Organization objectives, despite starting with a limited dataset. The model requires additional research to enhance its predictive accuracy using larger datasets and real-time data collection, which will aid in achieving global environmental stewardship.

Assessment of soil radioactivity and associated health risks in the Haripur gas field, Bangladesh - M.M. Mahfuz Siraz; Musfik R. Fahim; Zulfiqar Hasan Khan; Mohammad Shafiqul Alam; Araf Mahmud; Md. Bazlar Rashid; Md. Shihab Uddin Shuvo; Mahbuba Begum; Jannatul Mawa Trishna; Mayeen Uddin Khandaker; Shams A.M. Issa; Hamid Osman; et al. (Isotopes in Environmental and Health Studies, 2025)

Phylogeny and pathogenicity of Lasiodiplodia species associated with gummosis and dieback of cashew (Anacardium occidentale L.) in Burkina Faso - Oumarou Zoéyandé Dianda; Yéri Jacqueline Kansie; Issa Wonni; Diana Fernandez (Physiological and Molecular Plant Pathology, 2025)

Sustainable embankment contribute to a sustainable economy: The impact of climate change on the economic disaster in coastal area - Md. Abu Issa Gazi; Abdullah Al Masud; Md. Kazi Hafizur Rahman; Mohammad Bin Amin; Md. Emon; Abdul Rahman bin S Senathirajah; Masuk Abdullah (Environmental Development, 2025)

Energy efficiency in educational buildings: A systematic review of smart technology integration and occupant behaviour - Issa Chaer; Bertug Ozarisoy; Mubarak Abdelrasoul Elnour Ismail; Sanaz Salari; Ye Zhihui (Building and Environment, 2025)

Enhancement of genetic gain for early seedling vigor traits through marker-assisted pedigree selection in rice (Oryza sativa L.) - Sudhamani Kalluru; Issa Keerthi; Madhavilatha Kommana; D. M. Withanawasam; Eswarayya Ramireddy; D. Mohan Reddy; V. Umamahesh; Lakshminarayana R. Vemireddy (Physiology and Molecular Biology of Plants, 2025)

Targeting the double-edged sword: cytokines in the pathogenesis and treatment of autoimmune diseases - Fatima Dandash; Zahraa Salhab; Rawan Issa; Zeinab Al Dirani; Mariam Hamze; Gabriel Fares; Fatima Berro; Fatima Shaalan; Ali Hamade; Makram Merimi; Mehdi Najar; Rayan Dakroub; et al. (Inflammopharmacology, 2025)

Nitric oxide boosts antioxidant defense in olive trees against unexpected temperature drops - Sima Molazeinali; Vahid Niknam; Issa Karamatlou; Mehdi Hosseini-Mazinani (South African Journal of Botany, 2025)

Development of Cowpea (Vigna unguiculata) Mutant Lines for Dissecting Resilience to Drought Through Physiological and Molecular Crosstalk Analysis - Sara Diallo; François Abaye Badiane; Issa Diédhiou; Made Diouf; Mariama Ngom; Diaga Diouf (Plant Molecular Biology Reporter, 2025)

Geophysical investigation of groundwater potential and aquifer properties using ground magnetic and vertical electrical sounding at the University of Ilorin, Nigeria - Gabriel Efomeh Omolaiye; Sodiq Bamidele Adam; Taofeeq Ayinde Issa; Yusuf Magaji; Kayode Abdulhameed Oniyangi; Jimoh Ajadi; Saminu Olatunji; Oluwafemi Abdulmujeeb Oluyemoh; Ojulari Bashiru Alaba (Modeling Earth Systems and Environment, 2025)

Liquefaction Behavior of Suction Bucket Foundations for Wind Turbines Under Soil Variability - Mohammed Jasim Khammas Issa; Marwan Abdelsalam; Liqaa Hashim Khudhair; Mohsen Seyedi; Mohammad Shouib Anwar Khan (Geotechnical and Geological Engineering, 2025)

Development of Bacillus spp for controlling wilt disease and improving the growth of tomato - Najeeb M. Almasoudi; Nashwa M. A. Sallam; Esmat F. Ali; Abeer S. Alqurashi; Ahmed A. Issa; Fayez Althobaiti; Mohamed Housny; Hanan AlOmari; Kamal A. M. Abo-Elyousr (European Journal of Plant Pathology, 2025)

Maritime Pilotage and Sustainable Seaport: A Systematic Review - Seyed Behbood Issa-Zadeh; Claudia Lizette Garay-Rondero (Journal of Marine Science and Engineering, 2025)
The long-term sustainability of seaports depends on various operational factors, including infrastructure efficiency, digital innovation, environmental management, and regulatory compliance, among which maritime pilotage plays a crucial role in ensuring safe navigation and minimizing environmental, economic, and social risks. This research employed the PRISMA-ScR framework to evaluate the environmental, economic, and social impacts of pilotage on the sustainability of seaports. The findings demonstrate efficient navigation and spill avoidance, which reduce emissions, safeguard marine biodiversity, and maintain water quality. Economically, it reduces delays, optimizes operational expenses, and increases port competitiveness by increasing maritime traffic. Moreover, pilotage improves navigational safety, local professional skill development, and community interactions via ecological conservation and operational efficiency. It also indicates how environmental initiatives benefit the economy, increase port competitiveness, and promote job security and community happiness. The results also emphasize the significance of pilotage in sustainable seaport operations by quantifying pollution reductions, cost savings, and safety. The result also suggests that successful pilotage enhances ports’ viability and responsibility in global shipping networks while addressing environmental, economic, and social concerns.

Managing anthracnose fruit rot disease in pepper caused by Colletotrichum capsici via potash alum and frankincense essential oil - Mansour M. El-Fawy; Muhammad Imran; Esmat F. Ali; Abeer S. Alqurashi; Ahmed A. Issa; Rabee A. Emam; Mohamed F. Abd El-Mageed; Najeeb M. Almasoudi; Nashwa M. A. Sallam; Kamal A. M. Abo-Elyousr (Journal of Plant Pathology, 2025)

Antiradical and anti-acethylcholinesterase constituents from the methylene chloride extract of Ganoderma applanatum (Pers.) Pat (Ganodermataceae) and molecular docking study - Roméo Toko Feunaing; Joël Abel Gbaweng Yaya; Jean Noël Nyemb; Noël Issa Bassigue; Hervé Landry Ketsemen; Céline Henoumont; Antoine Kavaye Kandeda; Alessandro Venditti; Sophie Laurent; Emmanuel Talla (Natural Product Research, 2025)

Urban beach evolution in Saint Louis, Senegal (West Africa) using shore-based camera video monitoring as a management tool - Amadou Diouf; Cheikh Omar Tidjani Cissé; Rafael Almar; Baba Sy; Boubou Aldiouma Sy; Adelaide Taveneau; Issa Sakho; Bamol Ali Sow; Grégoire Abessolo Ondoa; Abdoulaye Ndour; Kader Ba; Erwin W.J. Bergsma; et al. (Regional Studies in Marine Science, 2025)

Recent advances in functionalized electrospun nanofiber membranes for enhanced oily water treatment - Issa Sulaiman Al-Husaini; Mansour Hamed Al Haddabi (Journal of Environmental Chemical Engineering, 2025)

Exploring the electrochemical potential of MoLa2O4/rGO/Co-MOF nanocomposites in energy storage and monosodium glutamate detection - Nimra Muzaffar; Imad Barsoum; Amir Muhammad Afzal; Muhammad Waqas Iqbal; Zubair Ahmad; Areej S. Alqarni; Shams A.M. Issa; H.M.H. Zakaly (Fuel, 2025)

Characterization and evaluation of physiochemical and microbiological water quality parameters in Palestinian schools: a case study from Central Hebron Directorate - Safa Sultan; Hassan Sawalha; Yaser Issa; Mohannad Nassar; Hatem Qaimari; Mohammad Abu Thrie; Maher Jabari (Euro-Mediterranean Journal for Environmental Integration, 2025)

Identification of moving sources in stochastic flow fields: A bayesian inferential approach with application to marine traffic in the mediterranean sea - Issam Lakkis; Alexios Rustom; Mohamad Abed El Rahman Hammoud; Leila Issa; Omar Knio; Olivier Le Maitre; Ibrahim Hoteit (Computational Geosciences, 2025)

Regulating microsomal triglyceride transfer protein with natural products for the treatment of hyperlipidaemia - Miral O. Sabry; Mohamed S. Sedeek; Sawsan M. El-Sonbaty; Marwa Y. Issa; Soheir M. El Zalabani (Natural Product Research, 2025)

Effect of corporate social responsibility on sustainable environmental performance: mediating effects of green capability and green transformational leadership; moderating effects of top management environmental concern and perceived organizational support - Md. Abu Issa Gazi; Md. Motaher Hossain; Shanta Islam; Abdullah Al Masud; Mohammad Bin Amin; Abdul Rahman bin S. Senathirajah; Masuk Abdullah (Environment, Development and Sustainability, 2025)
Corporate Social Responsibility (CSR) is increasingly acknowledged as an essential component of sustainable environmental performance (SEP), but the mechanisms behind this relationship are poorly understood, particularly in the case of SMEs in developing nations. Based on the Natural Resource-Based View (RBV) theory, this study investigates how green capability (GC) and green transformational leadership (GTL) mediate the CSR-SEP relationship, with a focus on the moderating function of perceived organizational support (POS). A survey of 420 SME employees in Bangladesh was undertaken, and the results were examined using SPSS and AMOS for structural equation modeling. The findings indicate that CSR greatly improves SEP. Furthermore, GC and GTL act as key mediators, increasing the CSR-SEP relationship. Furthermore, POS moderates the correlations between CSR and SEP, as well as GTL and SEP, implying that organizational support can strengthen or weaken these links. These findings demonstrate the diverse role of CSR in promoting environmental sustainability in many economic circumstances. The study provides practical implications for SMEs and policymakers, emphasizing the strategic significance of leadership and organizational support in improving CSR-driven sustainability efforts.

Structured timeline mapping as a data collection methodology: a new perspective for research on environmental adaptation - Jelena Luyts; Nathalie Burnay; Etienne Piguet; Arona Fall; Issa Mballo; Florence De Longueville; Sabine Henry (Climate and Development, 2025)

Hybrid retrofitting for upgrading the seismic performance of adjacent bridges vulnerable to different damage modes including pounding - Jumana Hasina; Aman Mwafy; Anas Issa; M. Shahria Alam (Engineering Structures, 2025)

The Influence of Tidal Distortion on Extreme Water Levels in Casamance Estuary, Senegal - Amadou Diouf; Issa Sakho; Bamol Ali Sow; Julien Deloffre; Marcellin Samou Seujip; Mouhamadoul Bachir Diouf; Robert Lafite (Estuaries and Coasts, 2025)

Biosynthesis of trimetallic nanoparticles and their biological applications: a recent review - Amr H. Hashem; Ebrahim Saied; Bahaa M. Badr; Mohamed Soliman Dora; Mahmoud A. Diab; Amer Morsy Abdelaziz; Fathy M. Elkady; Mohamed Abdelrahman Ali; Nasser Ibrahim Issa; Ziad A. Hamdy; Mohamed E. Nafea; Ahmed Nageh Khalifa; et al. (Archives of Microbiology, 2025)

Short alternating light/dark periods priming improves tobacco (Nicotiana tabacum L.) tolerance to clomazone herbicide: growth, chlorophyll a fluorescence transient and photosynthesis rate - Majd Darwish; Chayma Ouhibi; Habib Issa Abboud; Hala Adnan Alajouria; Félicie Lopez-Lauri; Huguette Sallanon (Acta Physiologiae Plantarum, 2025)

Connectivity and boundaries revisited: Livestock herders and parks in Central Africa - Matthew D. Turner; Leif Brottem; Hissein Abakar Zaid; Michael Eggen; Issa Hamid Bourdjo (Biological Conservation, 2025)

Study of Hydrogeochemical Properties of Surface Water (Case Study: Comparison of Two Adjacent Catchments, Cheshmeh Kileh and Shiroud, Northern Iran) - Nikoo Shiroud Issa; Alireza Ganji; Ali Moghimi Kandelous; Saeid Hakimi Asiabar (International Journal of Environmental Research, 2025)

Prevalence of Theileria Equi and Babesia Caballi and Associated Hemato-Biochemical Changes in Racing Horses in Erbil Province, Iraq - Khalid Jabar Aziz; Lokman Taib Omer AL- barwary; Nawzat Aboziad Issa; Muhsin Jamil Abdulwahid (Acta Parasitologica, 2025)

Tensile Force Limits of the Sheep Spine: Comparison to Forces Required to Extricate Grain Entrapped Victims - Salah F. Issa; Mahmoud S. Issa; Eric Nauman; Carl Wassgren; Charles Schwab; Zahab S. Ahsan; Mahmoud Nour; William Field (Journal of Agromedicine, 2025)

Comparative analysis of SDGs implementation: Testing a novel assessment framework approach - L. Issa; M. El-Fadel (Environmental Impact Assessment Review, 2025)

Design of New Wet Heterogeneous Photo Oxidation Process for Refinery Waste Water Treatment in Photo Baffled Reactor - Yousif. S. Issa; Qahtan A. Mahmood; Jasim I. Humadi; Ghanim Hassan; Rajesh Haldhar (Water, Air, & Soil Pollution, 2025)

Radioactive assessments of concrete modified with recycled waste materials - Solomon Oyebisi; Mahaad Issa Shammas; Oluwatoyin Ayeni; Hamis Samaila (Earth Science Informatics, 2025)

Modelling radium equivalent activity from 226Ra, 232Th, and 40K series of recycled waste materials: Analytical and artificial intelligence approaches - Solomon Oyebisi; Mahaad Issa Shammas; P. Jagadesh; Hilary Owamah; Miracle Olanrewaju Oyewola (Earth Science Informatics, 2025)

Comprehensive tsunami hazard assessment for Wudam As-Sahil, Northern Oman: Integrating deterministic and probabilistic approaches - Issa El-Hussain; Zaid Al-Habsi; Rachid Omira; Ahmed Deif; Adel Mohamed; Maria Ana Baptista; Yousuf Al-Shijbi (Arabian Journal of Geosciences, 2025)

Determination of noise levels and effects in noise sensitive areas case study: Sakarya province Serdivan district of Turkey - Rabia Köklü; Asude Ateş; Issa Al-Harthy (Environmental Monitoring and Assessment, 2024)

Monitoring the coastal–offshore water interactions in the Levantine Sea using ocean color and deep supervised learning - Georges Baaklini; Julien Brajard; Leila Issa; Gina Fifani; Laurent Mortier; Roy El Hourany (Ocean Science, 2024)
Understanding and tracking the surface circulation of the Levantine Sea present significant challenges, particularly close to the coast. This difficulty arises due to two main factors: the limited availability of in situ observations and the increasing inaccuracies in altimetry data close to the coastline. Here, we propose a new approach to monitor the interaction between offshore and coastal waters. In this approach, we develop a pattern detection model using deep learning by training the U-Net model on ocean color data to track the interactions between the coastal and offshore water in the Levantine Sea. The results showed the presence of notable variations in the behavior of coastal currents as they progress northward beyond 33.8° E. As these coastal currents become increasingly unstable, they exhibit continuous pinching-off events that are missed by conventional observational tools. These pinching-off events, especially observed along the Lebanese coast, manifest in various patterns that evolve simultaneously. Typically, these patterns have a relatively short lifespan of a few weeks, appearing and disappearing rapidly. However, these structures can evolve into larger eddies that endure for over 4 months in some years, especially in the northern part of the Lebanese coasts. Although these structures could be observed during all the seasons, spring consistently records the lowest activity of these structures. Overall, we showed that the pinching-off events were always observed in the eastern part of the Levantine Sea. On the contrary, in the southern part, along the Egyptian coasts, the coastal flow is more stable in the southern region, where these events are less frequently observed, with more than 63 % of the total observations not exhibiting any pinching-off events. Moreover, when these events occur in the south, their spatial extent is notably limited. This research not only sheds light on previously missed (or underestimated) coastal current dynamics in the Levantine Sea but also highlights the crucial need to increase in situ observations to advance our understanding of this region's complex oceanographic processes.

Corrigendum to “Sequence stratigraphic architecture and depositional evolution of the early Eocene-early Miocene Al Jabal Al Akhdar carbonate successions, N Cyrenaica Promontory, NE Libya – Interplay of tectonics and eustasy” [J. Afr. Earth Sci. 220 (2024) 1–24 105438] - Muneer Abdalla; Salah Hassan; Akram Zafir; Abdlsaid Ibrahem; Ahmad Issa (Journal of African Earth Sciences, 2024)

Sequence stratigraphic architecture and depositional evolution of the early Eocene-early Miocene Al Jabal Al Akhdar carbonate successions, N Cyrenaica Promontory, NE Libya – Interplay of tectonics and eustasy - Muneer Abdalla; Salah Hassan; Akram Zafir; Abdlsaid Ibrahem; Ahmad Issa (Journal of African Earth Sciences, 2024)

Influence of organic and mineral fertilizers and a foliar biostimulant on the yield and nutritional quality of strawberries (Fragaria ×ananassa Duch.) under field conditions - Idriss Djoko Kouam; Synthia Moungang; Honoré Issa Koulagna; Germain Pierre Ntsoli; Roland Wilfried Titti; Aoudou Yaouba (Biochemical Systematics and Ecology, 2024)

Effectiveness of biochar and wood vinegar from guava trees in controlling Fusarium verticillioides and enhancing growth and anatomical traits of maize (Zea mays L.) - Mansour M. El-Fawy; Ayman S. Saeed; Mohamed K. Abou-Shlell; Mahmoud A. Soliman; Esmat F. Ali; Ahmed A. Issa; Kamal A. M. Abo-Elyousr; Muhammad Imran; Asmaa S. El-Nagar (Journal of Plant Diseases and Protection, 2024)

Correction to: Analysis of Elements and Effects of Common Disinfectants in Common Salad Vegetables - Fahimeh Tooryan; Mojtaba Moazzen; Issa Mohammadpour fard; Narges Anvar; Majid Arabameri; Nabi Shariatifar; Pegah Kargarghomsheh (Biological Trace Element Research, 2024)

Analysis of Elements and Effects of Common Disinfectants in Common Salad Vegetables - Fahimeh Tooryan; Mojtaba Moazzen; Issa Mohammadpour fard; Narges Anvar; Majid Arabameri; Nabi Shariatifar; Pegah Kargarghomsheh (Biological Trace Element Research, 2024)

Hydrocarbon-Source Correlation in the Obayied Sub-Basin, North Western Desert, Egypt: Controls on Generation of Natural Gas and Light Crude Hydrocarbon Blends - Mostafa Hassan; Mahmoud Lotfy Leila; Mohammed Ahmed; Ghalib Issa; Branimir Šegvić; Omar Hegab (Journal of Earth Science, 2024)

Selective apoptotic and genotoxic effects of pomegranate peel extract against human hepatocellular carcinoma HepG2 cell line - Wesam T. Basal; Medhat El-Sakka; Neima K. El-Sonousy; Aliaa M. Issa (Advances in Traditional Medicine, 2024)

Epigallocatechin gallate-rich fraction alleviates histamine-induced neurotoxicity in rats via inactivating caspase-3/JNK signaling pathways - Eman I. Hassanen; Hayam A. Mansour; Marwa Y. Issa; Marwa A. Ibrahim; Wafaa A. Mohamed; Mahmoud A. Mahmoud (Food and Chemical Toxicology, 2024)

The Azawak zebu bred at the Toukounous experimental centre in Niger: reproduction performance and estimation of genetic parameters - Adamou Karimou Ibrahim; Issa Moumouni; Chanono Mogueza (Tropical Animal Health and Production, 2024)

Biallelic variants in ERLIN1: a series of 13 individuals with spastic paraparesis - Guillaume Cogan; Maha S. Zaki; Mahmoud Issa; Boris Keren; Marine Guillaud-Bataille; Florence Renaldo; Arnaud Isapof; Pauline Lallemant; Giovanni Stevanin; Lena Guillot-Noel; Thomas Courtin; Julien Buratti; et al. (Human Genetics, 2024)

Determination of polycyclic aromatic hydrocarbons (pahs) in mothers’ milk of kafr el-zayat district, egypt: A case study for the health risk of infants in urban regions - Asmaa Bayoumi Issa; Helmy Aly Ibrahim Anber; Sobhy Abdel-Rahiem Hamed; Fayza Ahmed Seddik; Khaled Yassin Abdel-Halim (Environmental Monitoring and Assessment, 2024)

First report of rust disease caused by Puccinia Porri on Egyptian leek in Egypt and its control by bergamot essential oil - Kamal A. M. Abo-Elyousr; Najeeb M. Almasoudi; Mansour M. El-Fawy; Ayman S. Saeed; Sameh H. E. Hamada; Esmat F. Ali; Ahmed A. Issa; Fayez Althobaiti; Ehab E. E. Korrat (Journal of Plant Pathology, 2024)

Clinical and Molecular Profiles of a Cohort of Egyptian Patients with Collagen VI-Related Dystrophy - Wessam E. Sharaf-Eldin; Karima Rafat; Mahmoud Y. Issa; Hasnaa M. Elbendary; Noura R. Eissa; Bahaa Hawaary; Nagwa E. A. Gaboon; Reza Maroofian; Joseph G. Gleeson; Mona L. Essawi; Maha S. Zaki (Journal of Molecular Neuroscience, 2024)
Collagen VI-related dystrophies (COL6-RD) display a wide spectrum of disease severity and genetic variability ranging from mild Bethlem myopathy (BM) to severe Ullrich congenital muscular dystrophy (UCMD) and the intermediate severities in between with dual modes of inheritance, dominant and recessive. In the current study, next-generation sequencing demonstrated potential variants in the genes coding for the three alpha chains of collagen VI ( COL6A1 , COL6A2 , or COL6A3 ) in a cohort of Egyptian patients with progressive muscle weakness ( n = 23). Based on the age of disease onset and the patient clinical course, subjects were diagnosed as follows: 12 with UCMD, 8 with BM, and 3 with intermediate disease form. Fourteen pathogenic variants, including 5 novel alterations, were reported in the enrolled subjects. They included 3 missense, 3 frameshift, and 6 splicing variants in 4, 3, and 6 families, respectively. In addition, a nonsense variant in a single family and an inframe variant in 3 different families were also detected. Recessive and dominant modes of inheritance were recorded in 9 and 8 families, respectively. According to ACMG guidelines, variants were classified as pathogenic ( n = 7), likely pathogenic ( n = 4), or VUS ( n = 3) with significant pathogenic potential. To our knowledge, the study provided the first report of the clinical and genetic findings of a cohort of Egyptian patients with collagen VI deficiency. Inter- and intra-familial clinical variability was evident among the study cohort.

Morphological adaptation to environmental stress in small ruminants from the sahelian zones of Niger and potential associations with carcass yield - Ibrahim Adamou Karimou; Hassane Yaye Abdou; Issoufou Guero Chekaraou; Moumouni Issa (Journal of Thermal Biology, 2024)

Active strike-slip faulting, diapirism and seismic hazards. The case of the Kareh Bas fault and the associated Dandenjan salt extrusion in the zagros Mountains, SW Iran - Francisco Gutiérrez; Issa Ilyati; Mohsen Rezaei; Mehdi Zarei; Michael Hudec (Journal of Structural Geology, 2024)

In vivo and ex vivo gene therapy for neurodegenerative diseases: a promise for disease modification - Pouya Ebrahimi; Elham Davoudi; Razieh Sadeghian; Amin Zaki Zadeh; Emran Razmi; Reza Heidari; Mohammad Hossein Morowvat; Issa Sadeghian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

A cost-benefit analysis of ecosystem services from restoring degraded soils to forest ecosystems in the Sahel - Sibiry Albert Kaboré; Emmanuelle Quillérou; Stéphanie Maiga-Yaleu; Maguette Kairé; Ibrahim Bouzou Moussa; Oumarou Malam Issa; Damien Hauswirth; Hassan Bismarck Nacro (Journal for Nature Conservation, 2024)

Glioblastoma stem cell metabolism and immunity - Joseph Hawly; Micaela G. Murcar; Alejandro Schcolnik-Cabrera; Mark E. Issa (Cancer and Metastasis Reviews, 2024)

Diagenesis and geochemistry of the lower Permian Ingleside Formation, Owl Canyon area, Larimer County, Colorado, USA - Ahmad Issa; Muneer Abdalla; Salah Hassan; Akram Zafir (Carbonates and Evaporites, 2024)

Pythium and Globisporangium species associated with cucumber rhizosphere causing damping-off and their effects on cucumber seed decay in Oman - Issa Hashil Al-Mahmooli; Maria Renate Finckh; Rethinasamy Velazhahan; AlMohanad Mohammed AlJabri; Adnan Šišić; Shah Hussain; Raid Abdel-Jalil; Abdullah Mohammed Al-Sadi (Archives of Microbiology, 2024)

Nuclear power plant biological complications on marine biota from a probabilistic accident – A case study - Akbar Abbasi; Fatemeh Mirekhtiary; Shams A.M. Issa; Merfat Algethami; Hesham M.H. Zakaly (Marine Pollution Bulletin, 2024)

Radioactivity concentration levels and potential radiotoxicity risk assessment of aquatic superfoods case study of algae supplements - Akbar Abbasi; Shams A.M. Issa; Fatemeh Mirekhtiary; Merfat Algethami; Hesham M.H. Zakaly (Marine Pollution Bulletin, 2024)

Unveiling the Sensitivity Analysis of Port Carbon Footprint via Power Alternative Scenarios: A Deep Dive into the Valencia Port Case Study - Seyed Behbood Issa-Zadeh; M. Dolores Esteban; José-Santos López-Gutiérrez; Claudia Lizette Garay-Rondero (Journal of Marine Science and Engineering, 2024)
The Port of Valencia, a prominent maritime center, is actively working towards minimizing its carbon emissions and aims to become a completely carbon-neutral port soon. This research uses data-driven sensitivity analysis to explore realistic power-generating options for a seaport to reduce its emissions. This approach comprises changing key parameters in power consumption and deploying renewable energies (rather than electricity and infrastructure prices, which are beyond the scope of this study) to assess their impact on the port’s overall emissions profile. Through sensitivity analysis, policymakers and managers discover each scenario’s efficacy and find the best decarbonization strategies. After thoroughly examining four realistic scenarios, our research findings show that each scenario’s emission reduction share and sensitivity are practical and feasible. It becomes clear that gradually replacing traditional fossil fuels for electricity generation with renewables is a reasonable and realistic option for emissions reduction. The results demonstrate that focusing on reasonable targets, such as replacing 30% and 50% of electricity generation with renewables, is more achievable and beneficial in the medium term than ambitious goals, like replacing all electricity with renewable energy. This research contributes to reducing emissions of the Port of Valencia by using data-driven sensitivity analysis to find practical renewable energy strategies. It provides actionable insights for managers and policymakers to implement feasible decarbonization plans, emphasizing gradual adoption of renewables over ambitious goals, thus supporting sustainable maritime operations.

The mollifying effect of Sambucus nigra extract on StAR gene expression, oxidative stress, and apoptosis induced by fenpropathrin in male rats - Marsail S. Nashed; Eman I. Hassanen; Marwa Y. Issa; Adel F. Tohamy; Abdelbary M. Prince; Ahmed M. Hussien; Maher M. Soliman (Food and Chemical Toxicology, 2024)

Kale (Brassica oleracea L. var. acephala) rhizosphere bacteria suppress Pythium aphanidermatum-induced damping-off of cabbage, produce biofilm and antimicrobial volatile compounds - Al-Galya Essa Al-Rubkhi; Abdullah Mohammed Al-Sadi; Rhonda Janke; Issa Hashil Al-Mahmooli; Majida Mohammed Ali Al-Harrasi; Rethinasamy Velazhahan (Australasian Plant Pathology, 2024)

Virulence and pangenome analysis of Vibrio harveyi strains from Greek and Red Sea marine aquaculture - Adriana Triga; Zeenat Atinuke Issa; Maria Smyrli; Linda Fenske; Pantelis Katharios (Aquaculture, 2024)

MicroRNA mmu-miR-511-5p: A promising Diagnostic Biomarker in Experimental Toxoplasmosis Using Different Strains and Infective Doses in Mice with Different Immune States Before and After Treatment - Rasha Fadly Mady; Mona Mohamed El-Temsahy; Yasmine Amr Issa; Aya Saied Zaghloul; Safaa Ibrahim Khedr (Acta Parasitologica, 2024)
Purpose Searching for a novel early diagnostic biomarker for toxoplasmosis, real-time-PCR was currently used to measure the serum mmu-miR-511-5p level in male Swiss-albino mice infected with either; ME49 or RH Toxoplasma gondii ( T. gondii ) strains. Methods Three mice groups were used; (GI) constituted the non-infected control group, while (GII) and (GIII) were experimentally infected with ME49 or RH strains, respectively. GII mice were orally infected using 10 or 20 ME49 cysts (ME-10 and ME-20), both were subdivided into; non-treated (ME-10-NT and ME-20-NT) and were further subdivided into; immunocompetent (ME-10-IC and ME-20-IC) [euthanized 3-days, 1, 2, 6 or 8-weeks post-infection (PI)], and immunosuppressed using two Endoxan ® injections (ME-10-IS and ME-20-IS) [euthanized 6- or 8-weeks PI], and spiramycin-treated (ME-10-SP and ME-20-SP) that received daily spiramycin, for one-week before euthanasia. GIII mice individually received 2500 intraperitoneal RH strain tachyzoites, then, were subdivided into; non-treated (RH-NT) [euthanized 3 or 5-days PI], and spiramycin-treated (RH-SP) that were euthanized 5 or 10-days PI (refer to the graphical abstract). Results Revealed significant upregulation of mmu-miR-511-5p in GII, one-week PI, with gradually increased expression, reaching its maximum 8-weeks PI, especially in ME-20-NT group that received the higher infective dose. Immunosuppression increased the upregulation. Contrarily, treatment caused significant downregulation. GIII recorded significant upregulation 3-days PI, yet, treatment significantly decreased this expression. Conclusion Serum mmu-miR-511-5p is a sensitive biomarker for early diagnosis of ME49 and RH infection (as early as one-week and 3-days, respectively), and its expression varies according to T. gondii infective dose, duration of infection, spiramycin-treatment and host immune status. Graphical abstract

Global Patterns of Agricultural Machine and Equipment Injuries- A Systematic Literature Review - Mian Muhammad Sajid Raza; Sihan Li; Salah F. Issa (Journal of Agromedicine, 2024)

Agricultural Injury Surveillance in the United States and Canada: A Systematic Literature Review - Sihan Li; Mian Muhammad Sajid Raza; Salah Issa (Journal of Agromedicine, 2024)

Biodegradation of petroleum hydrocarbons using a novel bacterial strain isolated from hydrocarbons contaminated soil of Saudi Arabia - Mohammad Hazaimeh; Belal Muneeb Kanaan; Faleh A. AlFaleh; Mahmoud M. Elhaig; Emran Issa Khamaiseh; Qamar Zia; Mohammed Alaidarous; Chandra Shekhar Seth; Noorah Alsowayeh; Faheem Ahmad (Biocatalysis and Agricultural Biotechnology, 2024)

Effects of decreasing roughage NDF in diets with high inclusion of DDGS on performance, feeding behavior, and ruminal parameters in Nellore bulls - Gabriel Namor Issa David; Alana Maria Menezes Di Calaça; Natalia de Almeida Leite; Taniela de Souza Conrado; Izadora Mazagão Veloso; Alessandro Rodrigues Costa Filho; Felipe de Souza Galvão; Yasmin Machado Barreto; Luan de Oliveira Moura Silva; Victor Rezende Moreira Couto; Juliano José de Resende Fernandes (Livestock Science, 2024)

Mechanical characterisation of the stones of Notre-Dame de Paris by in situ acoustic velocity measurement - Nathalie Domede; Thomas Parent; Colin Guenser; Ali Boukham; Pierre Morenon; Aboubacar Sadikou Issa-Ibrahim (International Journal of Rock Mechanics and Mining Sciences, 2024)

Potential of oligonucleotide- and protein/peptide-based therapeutics in the management of toxicant/stressor-induced diseases - Issa Sadeghian; Mina Akbarpour; Fatemeh Mohammad Alizadeh Chafjiri; Pegah Mohammad Alizadeh Chafjiri; Reza Heidari; Mohammad Hossein Morowvat; Razieh Sadeghian; Mohammad Javad Raee; Manica Negahdaripour (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Effect of greywater treated by horizontal subsurface flow wetlands planted with Chrysopogon zizanioides and Andropogon gayanus on the germination of tomato (Lycopersicon esculentum Mill.) seeds under Sahelian climate - Cheik Omar Tidiane Compaoré; Ynoussa Maiga; Issa Nagalo; Mamady Sawadogo; Sandrine G. Zongo; Oumarou Mien; Mahamadi Nikièma; Amidou S. Ouili; Iliassou Mogmenga; Cheik Amadou Tidiane Ouattara; James R. Mihelcic; Aboubakar Sidiki Ouattara (Ecological Engineering, 2024)

Isocyanide-based synthesis of spirorhodanine-cyclopentadiene and spirorhodanine-iminobutenolide conjugates from Winterfeldt’s zwitterions and 5-ylidene rhodanines - Issa Yavari; Sara Sheikhi; Zohreh Taheri (Molecular Diversity, 2024)

Formation of bis-spiropyrrolidines from isatin, secondary amines, and alkylidene Meldrum’s acids - Samira Khandan; Issa Yavari (Molecular Diversity, 2024)

A synthesis of functionalized 3-amino-1,2,4-triazoles from nitrile imines and guanidine derivatives - Issa Yavari; Zohreh Taheri; Sara Sheikhi (Molecular Diversity, 2024)

Synthesis of adamantane-monoterpene conjugates with 1,3,4-thiadiazol-2(3H)-imine linker and evaluation of their inhibitory activity against TDP1 - Aldar A. Munkuev; Alexandra L. Zakharenko; Tatyana E. Kornienko; Nadezhda S. Dyrkheeva; Ekaterina S. Ilina; Evgeniy V. Suslov; Fatima Issa; Chigozie Achara; Jóhannes Reynisson; Konstantin P. Volcho; Nariman F. Salakhutdinov; Olga I. Lavrik (Medicinal Chemistry Research, 2024)

Can network analysis ascertain SDGs interlinkages towards evidence-based policy planning? A systematic critical assessment - Lea Issa; Toufic Mezher; Mutasem El Fadel (Environmental Impact Assessment Review, 2024)

The vocal repertoire and the daily calling activity of the Yellow-breasted Barbet (Trachyphonus margaritatus) - Mathieu Mahamoud-Issa; Bożena Sikora; Katarzyna Łosak; Tomasz S. Osiejuk (Journal of Ornithology, 2024)
The Yellow-breasted Barbet ( Trachyphonus margaritatus ) is a group-living and chorusing bird species. However, its vocal repertoire remains poorly described. In this study, we measured the acoustic features of four distinct vocalisations as well as the daily calling activity of barbets at 11 roosting cavity sites. We found that bird’s peak of calling activity is early in the morning and at the end of the day. The cohesion calls and group vocal displays were the most common vocalisations. Moreover, cohesion calls were often used before the start of a group vocal displays which suggests a function in the intra-group cohesiveness.

Plant-based foods and hepatocellular carcinoma: A review on mechanistic understanding - Raakia Anam Saeed; Maria Maqsood; Raafia Anam Saeed; Hafiz Shehzad Muzammil; Muhammad Issa Khan; Laiba Asghar; Sahar Un Nisa; Roshina Rabail; Rana Muhammad Aadil (Critical Reviews in Food Science and Nutrition, 2023)

Separation of rare earth elements using chelation-assisted electrodialysis - Sanaz Mosadeghsedghi; Maziar E. Sauber; Mohammadali Baghbanzadeh; Seyedeh Laleh Dashtban Kenari; Konstantin Volchek; Soha Issa; Saviz Mortazavi (Journal of Environmental Chemical Engineering, 2023)

Developing Functional Recharge Systems to Control Saltwater Intrusion via Integrating Physical, Numerical, and Decision-Making Models for Coastal Aquifer Sustainability - Yehia Miky; Usama Hamed Issa; Wael Elham Mahmod (Journal of Marine Science and Engineering, 2023)
Controlling the hydraulic heads along a coastal aquifer may help to effectively manage saltwater intrusion, improve the conventional barrier’s countermeasure, and ensure the coastal aquifer’s long-term viability. This study proposed a framework that utilizes a decision-making model (DMM) by incorporating the results of two other models (physical and numerical) to determine proper countermeasure components. The physical model is developed to analyze the behavior of saltwater intrusion in unconfined coastal aquifers by conducting two experiments: one for the base case, and one for the traditional vertical barrier. MODFLOW is used to create a numerical model for the same aquifer, and experimental data are used to calibrate and validate it. Three countermeasure combinations, including vertical barrier, surface, and subsurface recharges, are numerically investigated using three model case categories. Category (a) model cases investigate the hydraulic head’s variation along the aquifer to determine the best recharge location. Under categories (b) and (c), the effects of surface and subsurface recharges are studied separately or in conjunction with a vertical barrier. As a pre-set of the DMM, evaluation and classification ratios are created from the physical and numerical models, respectively. The evaluation ratios are used to characterize the model case results, while the classification ratios are used to classify each model case as best or worst. An analytical hierarchy process (AHP) as a DMM is built using the hydraulic head, salt line, repulsion, wedge area, and recharge as selection criteria to select the overall best model case. According to the results, the optimum recharging location is in the length ratio (LR) from 0.45 to 0.55. Furthermore, the DMM supports case3b (vertical barrier + surface recharge) as the best model case to use, with a support percentage of 48%, implying that this case has a good numerical model classification with a maximum repulsion ratio (Rr) of 29.4%, and an acceptable wedge area ratio (WAR) of 1.25. The proposed framework could be used in various case studies under different conditions to assist decision-makers in evaluating and controlling saltwater intrusion in coastal aquifers.

Proactive policy options for drought resilience in the Sahel region - Aboubakr Gambo Boukary; Issa Garba; Zakari Seybou Abdourahamane; Alisher Mirzabaev (Journal of Arid Environments, 2023)

Discrimination between hypervirulent and non-hypervirulent ribotypes of Clostridioides difficile by MALDI-TOF mass spectrometry and machine learning - Ahmed Mohamed Mostafa Abdrabou; Issa Sy; Markus Bischoff; Manuel J. Arroyo; Sören L. Becker; Alexander Mellmann; Lutz von Müller; Barbara Gärtner; Fabian K. Berger (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Hypervirulent ribotypes (HVRTs) of Clostridioides difficile such as ribotype (RT) 027 are epidemiologically important. This study evaluated whether MALDI-TOF can distinguish between strains of HVRTs and non-HVRTs commonly found in Europe. Obtained spectra of clinical C. difficile isolates (training set, 157 isolates) covering epidemiologically relevant HVRTs and non-HVRTs found in Europe were used as an input for different machine learning (ML) models. Another 83 isolates were used as a validation set. Direct comparison of MALDI-TOF spectra obtained from HVRTs and non-HVRTs did not allow to discriminate between these two groups, while using these spectra with certain ML models could differentiate HVRTs from non-HVRTs with an accuracy >95% and allowed for a sub-clustering of three HVRT subgroups (RT027/RT176, RT023, RT045/078/126/127). MALDI-TOF combined with ML represents a reliable tool for rapid identification of major European HVRTs.

Optimizing Smart Energy Infrastructure in Smart Ports: A Systematic Scoping Review of Carbon Footprint Reduction - Seyed Behbood Issa Zadeh; Maria Dolores Esteban Perez; José-Santos López-Gutiérrez; Gonzalo Fernández-Sánchez (Journal of Marine Science and Engineering, 2023)
To lessen the environmental impact of the maritime industry, ports must decarbonize in conformity with various standards such as the European Green Deal and the Sustainable Development Goals (SDGs). In this regard, they must demonstrate integrated low-emission energy production, distribution, and supply, as well as sustainable alternative infrastructure for refueling ships, cargo handling equipment, and other vehicles inside port boundaries. To address this issue, ports must progress toward smartening their operations. This requires intelligent infrastructure and components, with smart energy infrastructure being one of the most crucial ones. It is a part of port energy management systems (EMSs) and works based on modern technology to balance energy demand, distributions, and supply while transitioning to renewable energies. This study investigates the “scoping review” of “smart energy infrastructure” deployment and its efficiency in seaport EMSs to reduce the port’s carbon footprint (C.F). The “Introduction” section discusses the subject’s significance. The “Materials and Methods” section explains the process of selecting and revising references and relevant material. The “Findings” section then examines the several aspects and sections of a smart port and smart energy infrastructure, as well as how they function. The “Discussion” section explains the interpretation based on the present situation. Finally, the “Conclusion” part gives scientific thoughts and comments on the work-study debate and ideas for future research in the same field to help port authorities achieve sustainability.

Quality assessment of Vitellaria paradoxa seed oil obtained under different extraction conditions and solvents - Ibanga O. Isaac; Iniobong S. Enengedi; Issa A. Abdulazeez (Sustainable Chemistry and Pharmacy, 2023)

Effects of citrus pomace on mechanical, sensory, phenolic, antioxidant, and gastrointestinal index properties of corn extrudates - Muhammad Asif; Muhammad Kashif Iqbal Khan; Muhammad Issa Khan; Abid Aslam Maan; Harrison Helmick; Jozef L. Kokini (Food Bioscience, 2023)

Full-scale testing and nonlinear finite element analysis of a pioneering fully prefabricated noise barrier wall system - Ahmad G. Elrefae; Mohsen A. Issa (Engineering Structures, 2023)

Developing an integrated mathematical model of fermentation-pervaporation system for bioethanol production - Hamid Zentou; Zurina Z. Abidin; Mohammed Abdullah Issa; Robiah Yunus; Dayang Radiah Awang Biak (Chemical Engineering Journal, 2023)

A consecutive synthesis of spiro[cyclopenta[b]pyrrole-5,2′-indene] derivatives via spirocyclization/annulation reactions - Azadeh Parhami; Issa Yavari; Gholam Reza Najafi (Molecular Diversity, 2023)

A Novel Mutation in the MAP7D3 Gene in Two Siblings with Severe Intellectual Disability and Autistic Traits: Concurrent Assessment of BDNF Functional Polymorphism, X-Inactivation and Oxidative Stress to Explain Disease Severity - Marwa Kharrat; Abir Ben Issa; Abdelaziz Tlili; Olfa Jallouli; Olfa Alila-Fersi; Marwa Maalej; Jihen Chouchen; Yosra Ghouylia; Fatma Kamoun; Chahnez Triki; Faiza Fakhfakh (Journal of Molecular Neuroscience, 2023)

An integrated one-dimensional geomechanical model to identify the optimal mud weight and the well trajectory for the Zubair formation - Mustafa Adil Issa; Farqad Ali Hadi; Ali Nooruldeen Abdulkareem; Muntadher Adil Issa; Runar Nygaard (Arabian Journal of Geosciences, 2023)

Timing of the reproductive cycle of Holothuria (Mertensiothuria) leucospilota (Brandt, 1835) from the Persian Gulf based on evaluation of gonad histomorphology and sex hormones - Fatemeh Azimiyan Faridani; Negin Salamat; Babak Doostshenas; Issa Sharifpour; Ali Fakhri (Aquatic Sciences, 2023)

The association of in-utero exposure to polycyclic aromatic hydrocarbons and umbilical liver enzymes - Li Wanying; Mariami T. Okromelidze; Andrés Alexis Ramírez-Coronel; Angelina O. Zekiy; Rasha Fadhel Obaid; Zanko Hassan Jawhar; Gamal A. Gabr; Mais Mazin Al-Hamdani; Sokaina Issa Kadhim; Yasser Fakri Mustafa; Moslem Lari Najafi; Mohammad Miri (Science of The Total Environment, 2023)

In Vitro Filaricidal Properties of Hydro-Methanolic Extracts of Powdery Fractions of Khaya senegalensis (Meliaceae) on Onchocerca ochengi - Borris Rosnay Galani Tietcheu; Theodore Betrosse; Rene Bilingwe Ayiseh; Emmanuel Issa Yuunoeoene; Emmanuel Mfotie Njoya; Francis Nveikoueng; Nicolas Yanou Njintang; Dieudonne Ndjonka (Acta Parasitologica, 2023)

Biosynthesis of zinc oxide nanoparticles using the supernatant of Weissella cibaria UPM22MT06 and its antibacterial and cytotoxicity properties - Ahmed Issa Al-Tameemi; Mas Jaffri Masarudin; Raha Abdul Rahim; Toby Mills; Verlaine J Timms; Brett A Neilan; Nurulfiza Mat Isa (Biologia, 2023)

Comprehensive review on the efficiency of ionic liquid materials for membrane separation and environmental applications - Weidong Li; Duaa Abdul Rida Musa; Nafis Ahmad; Mohaned Adil; Usama S. Altimari; Abdullah Khaleel Ibrahim; A.M. Alshehri; Yassin Riyahi; Asala Salam Jaber; Sokaina Issa Kadhim; Anastasia Andreevna Rushchitc; Mutlaq Owaidh Aljuaid (Chemosphere, 2023)

An atypical expression of core α-Dystroglycan and Laminin-α2 in skin fibroblasts of patients with congenital muscular dystrophies - Sahar Sabry; Mahmoud Y Issa; Mohamed S Abdel-Hamid; Noura R Eissa; Sherif F Abdel-Ghafar; Mona M Ibrahim; Maha S Zaki (Molecular Biology Reports, 2023)
Background Congenital muscular dystrophies (CMDs) result from genetically inherited defects in the biosynthesis and/or the posttranslational modification (glycosylation) of laminin-α2 and α-dystroglycan (α-DG), respectively. The interaction between both proteins is responsible for the stability and integrity of the muscle cell. We aimed to study the expression profiles of both proteins in two classes of CMDs. Subjects and methods Whole-exome sequencing (WES) was done for four patients with neuromuscular manifestations. The expression of core α-DG and laminin-α2 subunit in skin fibroblasts and MCF-7 cells was assessed by western blot. Results WES revealed two cases with nonsense mutations; c.2938G > T and c.4348 C > T, in LAMA2 encodes laminin-α2. It revealed also two cases with mutations in POMGNT1 encode protein O-mannose beta-1,2-N-acetylglucosaminyltransferase mutations. One patient had a missense mutation c.1325G > A, and the other had a synonymous variant c.636 C > T. Immunodetection of core α-DG in skin fibroblasts revealed the expression of truncated forms of core α-DG accompanied by reduced expression of laminin-α2 in POMGNT1-CMD patients and one patient with LAMA2-CMD. One patient with LAMA2-CMD had overexpression of laminin-α2 and expression of a low level of an abnormal form of increased molecular weight core α-DG. MCF-7 cells showed truncated forms of core α-CDG with an absent laminin-α2. Conclusion A correlation between the expression pattern/level of core α-DG and laminin-α2 could be found in patients with different types of CMD.

Effects of Sporosarcina Pasteurii’s on Curing Time and Strength of Silty Sand Soil - Alireza Karami; Issa Shooshpasha; Hosein Ali Alikhani (Geotechnical and Geological Engineering, 2023)

A comprehensive review on adsorption of methylene blue dye using leaf waste as a bio-sorbent: isotherm adsorption, kinetics, and thermodynamics studies - Zainab Haider Mussa; Lubna Raad Al-Ameer; Fouad Fadhil Al-Qaim; Issa Farhan Deyab; Hesam Kamyab; Shreeshivadasan Chelliapan (Environmental Monitoring and Assessment, 2023)

Bildbasierte Durchflussmessverfahren für das Monitoring von Hochwasserereignissen - Issa Hansen; Thomas Engstle; Jakob Menzinger; Beat Lüthi; Salvador Peña-Haro (WASSERWIRTSCHAFT, 2023)

Intermuscular Coherence in Spinocerebellar Ataxias 3 and 6: a Preliminary Study - Naoum P. Issa; Serdar Aydin; Shail Bhatnagar; Nicholas W. Baumgartner; Jacquelyn Hill; Sravya Aluri; Chloe S. Valentic; Eric Polley; Christopher M. Gomez; Kourosh Rezania (The Cerebellum, 2023)
Spinocerebellar ataxias (SCAs) are familial neurodegenerative diseases involving the cerebellum and spinocerebellar tracts. While there is variable involvement of corticospinal tracts (CST), dorsal root ganglia, and motor neurons in SCA3, SCA6 is characterized by a pure, late-onset ataxia. Abnormal intermuscular coherence in the beta-gamma frequency range (IMCβγ) implies a lack of integrity of CST or the afferent input from the acting muscles. We test the hypothesis that IMCβγ has the potential to be a biomarker of disease activity in SCA3 but not SCA6. Intermuscular coherence between biceps brachii and brachioradialis muscles was measured from surface EMG waveforms in SCA3 ( N = 16) and SCA6 ( N = 20) patients and in neurotypical subjects ( N = 23). IMC peak frequencies were present in the β range in SCA patients and in the γ range in neurotypical subjects. The difference between IMC amplitudes in the γ and β ranges was significant when comparing neurotypical control subjects to SCA3 ( p < 0.01) and SCA6 ( p = 0.01) patients. IMCβγ amplitude was smaller in SCA3 patients compared to neurotypical subjects ( p < 0.05), but not different between SCA3 and SCA6 patients or between SCA6 and neurotypical subjects. IMC metrics can differentiate SCA patients from normal controls.

First records about oxygen consumption by Chironomus sancticaroli (Diptera: Chironomidae): an analysis using microsensors - Juliano J. Corbi¹; Carina Graminha Issa¹; Antônio Wagner Lamon¹ (Biologia, 2023)

Lasiodiplodia species associated with mango (Mangifera indica L.) decline in Burkina Faso and influence of climatic factors on the disease distribution - Oumarou Zoéyandé Dianda; Issa Wonni; Léonard Ouédraogo; Philippe Sankara; Charlotte Tollenaere; Emerson M. Del Ponte; Diana Fernandez (Physiological and Molecular Plant Pathology, 2023)

Geo-spatial modelling of carbon stock assessment of date palm at different age stages: An integrated approach of fieldwork, remote sensing and GIS - Basam Dahy; Salem Issa; Nazmi Saleous (Ecological Modelling, 2023)

High multidrug resistance of Listeria monocytogenes and association with water sources in sheep and goat dairy flocks in Jordan - Mohammad M. Obaidat; Issa A. AlShehabat (Preventive Veterinary Medicine, 2023)

Extraction of dietary fiber and polyphenols from mango peel and its therapeutic potential to improve gut health - Amna Tariq; Amna Sahar; Muhammad Usman; Aysha Sameen; Marriam Azhar; Rimsha Tahir; Rimsha Younas; Muhammad Issa Khan (Food Bioscience, 2023)

Seismic response evaluation of spring-based piston braced frames by employing closed-loop dynamic (CLD) testing - Anas Issa; Navid Rahgozar; M. Shahria Alam (Engineering Structures, 2023)

Association of DRB1*11 and DRB1*12 alleles of the HLA system with the evolution of the Hepatitis B virus infection in Burkina Faso - Sidnooma Véronique Zongo; Florencia Wendkuuni Djigma; Albert Théophane Yonli; Pegdwendé Abel Sorgho; Bolni Marius Nagalo; Lassina Traore; Dogfounianalo Somda; Lanyo Jospin Amegnona; Eugène Languie; Couna Christiane Bere Some; Lydie Marie Jeannette Sia; Issa Boaffi Sourabie; et al. (Molecular Biology Reports, 2023)

Adsorption of methylene blue dye from aqueous solution using low-cost adsorbent: kinetic, isotherm adsorption, and thermodynamic studies - Safaa Talib Al-Asadi; Fouad Fadhil Al-Qaim; Haider Falih Shamikh Al-Saedi; Issa Farhan Deyab; Hesam Kamyab; Shreeshivadasan Chelliapan (Environmental Monitoring and Assessment, 2023)

A Framework for Accurate Carbon Footprint Calculation in Seaports: Methodology Proposal - Seyed Behbood Issa Zadeh; José Santos López Gutiérrez; M. Dolores Esteban; Gonzalo Fernández-Sánchez; Claudia Lizette Garay-Rondero (Journal of Marine Science and Engineering, 2023)
According to the 2020 European Sea Ports Organization Environmental Report, ports are the second biggest environmental concern for climate change due to greenhouse gas emissions. Furthermore, the International Association of Ports and Harbors determined that seaports are carbon-intensive and environmentally harmful because of increased commercial and non-commercial activities surrounding them. Due to the urgent concern to address solutions in this research line, this study aims to present a frame of reference to estimate the Carbon Footprint in ports through an innovative method. The study design presents a Meta-Analyses Scoping Review based on the PRISMA-ScR methodology to analyse the current articles, normativity and primary resources related to the Carbon Footprint estimation approach in seaports. Then, a categorization for the new method of Carbon Footprint and scopes description calculation is presented. Besides, the Port of Valencia, a famous Spanish port, provides the case study to apply and confirm the approach. Findings state that this new approach, with the designation of new boundaries and factors affecting ports’ emissions would lead to an accurate estimation of the carbon footprint of ports. The originality and value of this work-study deliver scientific interpretations, reflections, and suggestions for future research and validation.

Building a geospatial model to identify potential geothermal sites in Ayrobera: Afar depression, NE Ethiopia - Biruk Abera Cherkose; Salem Issa; Hakim Saibi; Khalid ElHaj (Geothermics, 2023)

A review study summarizes the main characterization techniques of nano-composite photocatalysts and their applications in photodegradation of organic pollutants - Zaid H. Jabbar; Bassim H. Graimed; Ayah A. Okab; Mohammed Abdullah Issa; Saad H. Ammar; Hussein J. Khadim; Yasmeen A. Shafiq (Environmental Nanotechnology, Monitoring & Management, 2023)

Experimental investigation and seismic analysis of a novel self-centering piston-based bracing archetype with polyurethane cores - Anas Issa; Navid Rahgozar; M. Shahria Alam (Engineering Structures, 2023)

Contributions of constraints to mechanical fields of energy pile foundation - Hassan Abbaszadeh Amirdehi; Issa Shooshpasha (Innovative Infrastructure Solutions, 2023)

Predominance of Multidrug-Resistant Gram-Negative Bacteria on Contaminated Surfaces at a Tertiary Hospital in Tanzania: A Call to Strengthening Environmental Infection Prevention and Control Measures - Agricola Joachim; Joel Manyahi; Habiba Issa; Jackline Lwoga; Frank Msafiri; Mtebe Majigo (Current Microbiology, 2023)

The effects of the water-soluble fractions of crude oil on liver and kidney tissues of Caspian Kutum juveniles, Rutilus frisii - Fatemeh Heidary Jamebozorgi; Behrooz Abtahi; Issa Sharifpour; Jafar Seyfabadi; Zahra Taghizadeh Rahmatabadi; Samira Nazemroaya; Ebrahim Lari (Marine Pollution Bulletin, 2023)

Pollution assessment around a big city in West Africa reveals high concentrations of microplastics and microbiologic contamination - Amidou Sonko; Patrice Brehmer; Guillaume Constantin de Magny; Gaël Le Pennec; Bissoume Sambe Ba; Ousmane Diankha; Mamadou Fall; Isabelle Linossier; Maryvonne Henry; Issa N’Diaye; Saliou Faye; Yoba Kande; et al. (Regional Studies in Marine Science, 2023)

Stories of change in nutrition in Burkina Faso 1992–2018: a macro-level perspective - Zuzanna Turowska; Emilie Buttarelli; Issa Sombié; Nicholas Nisbett; Mara Van den Bold; Elodie Becquey (Food Security, 2023)
Looking back at the development of successful enabling environments for nutrition may inform policymakers on how to accelerate progress to end all forms of malnutrition by 2030. As under-five stunting declined substantially in Burkina Faso, from a peak at 45% in 1998/99 to 25% in 2018, we analyzed through a stories of change approach the actors, ideas, initiatives, policies and capacities which enabled wide-scale nutrition progress. We triangulated findings from policy analysis, stakeholder mapping, and national-level semi-structured interviews (n = 20). We found that since 2002, nutrition has been anchored in the Ministry of Health, where leadership advocated for the creation of coordination bodies, enabling a coherent defining of nutrition and laying groundwork for better integration of nutrition into and prioritization of nutrition by the health and tangential ministries. Under the leadership of the Ministry of Health and its partners, horizontal and vertical coherence in nutrition action increased, through effective cooperation between nutrition actors; increasing intersectoral collaboration, particularly with the influential agriculture sector; and increasing funding to support nutrition-sensitive programming and build the capacity of nutrition staff. Nevertheless, sustainably organizing funding and human resources at the decentralized level remained challenging, in a context of emerging threats such as climate change and insecurity. Burkina Faso’s health sector’s success in creating an enabling environment for nutrition may have contributed to improvements in child nutrition alongside other sectoral improvements. Enhancing accountability of the Health, Agriculture, WASH, Education and Social Protection sectors and empowering decentralized bodies to take nutrition-relevant decisions may help accelerating progress in nutrition.

The entire lifetime of a distinct double-diffusive staircase in crater Lake Nyos, Cameroon - Alfred Wüest; Issa; Christian Dinkel; Michael Halbwachs; Beat Müller (Environmental Fluid Mechanics, 2023)
Lake Nyos, a deep crater lake, located in the north-west of Cameroon, was permanently stratified below 50 m depth due to subaquatic sources supplying warm, salty and CO 2 -enriched water into the deepest reaches. The high CO 2 content in these source waters caused the 1986 limnic eruption. The deep inflowing water is denser than the hypolimnetic water and maintains the stability of the water column, which is double-diffusively stratified. During the dry season in Feb 2002, cooling triggered the formation of a double-diffusive (DD) staircase, a sequence of homogeneously mixed layers separated by distinct stable interfaces. The initiation of the staircase was slightly below the permanent chemocline at ~ 50 m depth, from where the staircase expanded vertically in a diffusion-type manner for ~ 750 days to a maximal vertical extension of ~ 37 m. The staircase pattern caused the upward heat fluxes to increase which depleted the driving temperature gradient. Subsequently, the density ratio increased and reduced the upward heat flux divergence until DD progressively weakened and finally the staircase structure eroded. Based on 39 CTD profiles, we describe the DD phenomenon, explain the three distinct phases of this unique DD event, which lasted for ~ 850 days, and discuss the vertical extension of the DD zone in relation to the rates of new layer formation and layer decay. To our knowledge, this is the only observation over the entire lifespan—“from birth to death”—of a DD event in a natural water body.

Geochemical characteristics of natural gases and source rocks in Obayied sub-basin, north Western Desert, Egypt: implications for gas-source correlation - Mostafa Hassan; Mahmoud Leila; Mohammed Ahmed; Ghalib Issa; Omar Hegab (Acta Geochimica, 2023)

Contribution of outdoor noise-induced health risk in schools located in urbanized arid country - Patrick Amoatey; Issa Al-Harthy; Diawuo Amankona; Stella Douban; Azizallah Izady; Mingjie Chen; Khalifa Al-Jabri; Mubarak Al-Alawi (Environmental Science and Pollution Research, 2023)

Roundtrip, free-floating and peer-to-peer carsharing: A Bayesian behavioral analysis - Érika Martins Silva Ramos; David Issa Mattos; Cecilia Jakobsson Bergstad (Transportation Research Part D: Transport and Environment, 2023)

Acid-induced improvement of photosensitizing efficiency of porphyrins under heterogeneous aqueous conditions: High photosensitizing activity, dissociative stability and photooxidative durability - Farzaneh Qodrati-nasrabadi; Issa Sardivand-chegini; Akram Heydari-turkmani; Saeed Zakavi (Journal of Environmental Chemical Engineering, 2023)

A new technique for removing the accumulated liquids in gas-condensate pipelines and risers by foam generation in the presence of mixed surfactants - Bahman ZareNezhad; Issa Zakeri (Fuel, 2023)

A one-pot synthesis 3-alkoxycarbonyl-3,4-dihydro-2H-pyran-2-ones from vinylidene melderum’s acids, dialkyl acetylenedicarboxylates, and simple alcohols - Samira Khandan; Issa Yavari; Javad Azizian (Molecular Diversity, 2023)

SARS-CoV-2-mediated liver injury: pathophysiology and mechanisms of disease - Ali Choaib; Elio Issa; Francesca El Choueiry; Jade Nasser Eldin; Khodor Shbaklo; Maryline Alhajj; Ramy Touma Sawaya; Ghaith Assi; Moni Nader; Rajaa Chatila; Wissam H. Faour (Inflammation Research, 2023)

The influence of seagrass and its associated sediment on organic carbon storage: A case of Halodule uninervis and Syringodium isoetifolium meadows of Western India Ocean, Tanzania - Liberatus Dominick Lyimo; Mariam Issa Hamisi (Marine Environmental Research, 2023)

Optimal parameters extracting of fuel cell based on Gorilla Troops Optimizer - Mohamed Abd Elaziz; Laith Abualigah; Mohamed Issa; Ahmed A. Abd El-Latif (Fuel, 2023)

The witzenhausen food inventory – organic food (WFI-OeL) an itemset for measuring consumers' attitudes and preferences for organic food in Germany - David Kühn; Thomas Krikser; Irwa Issa; Adriano Profeta (Food Quality and Preference, 2023)

Characterization of Seismic Source Zones in the Gulf of Aden Region - Ahmed Deif; Harith Al Kubaisy; Iman Farag Abu El-Nader; Issa El-Hussain; Yousuf Al-Shijbi; Adel M. E. Mohamed (Pure and Applied Geophysics, 2023)

Time-dependent association between omeprazole and esomeprazole and hospitalization due to hyponatremia - Issa Issa; Jakob Skov; Henrik Falhammar; Jan Calissendorff; Jonatan D. Lindh; Buster Mannheimer (European Journal of Clinical Pharmacology, 2023)
Purpose The aim of this study was to explore the time-course of hospitalization due to hyponatremia associated with omeprazole and esomeprazole. Methods In this register-based case–control study, we compared patients hospitalized with a main diagnosis of hyponatremia ( n = 11,213) to matched controls ( n = 44,801). We used multiple regression to investigate time-related associations between omeprazole and esomeprazole and hospitalization because of hyponatremia. Results The overall adjusted OR (aOR) between proton pump inhibitor (PPI) exposure, regardless of treatment duration and hospitalization with a main diagnosis of hyponatremia, was 1.23 (95% confidence interval CI 1.15–1.32). Exposure to PPIs was associated with a prompt increase in risk of hospitalization for hyponatremia from the first week (aOR 6.87; 95% CI 4.83–9.86). The risk then gradually declined, reaching an aOR of 1.64 (0.96–2.75) the fifth week. The aOR of ongoing PPI treatment was 1.10 (1.03–1.18). Conclusion The present study shows a marked association between omeprazole and esomeprazole and hyponatremia related to recently initiated treatment. Consequently, newly initiated PPIs should be considered a potential culprit in any patient suffering from hyponatremia. However, if the patient has had this treatment for a longer time, the PPI should be considered a less likely cause.

Cytoarchitecture, myeloarchitecture, and parcellation of the chimpanzee inferior parietal lobe - Laura D. Reyes; Young Do Kim; Habon Issa; William D. Hopkins; Scott Mackey; Chet C. Sherwood (Brain Structure and Function, 2023)

Assessment of Trace Metals in Camelus dromedarius Meat from Mauritania - El Boukhary Ahmed; Mohamed Salem El Mahmoud Hamed; Babah Sidi Moktar; Angelo Santana-Del Pino; Mohamed Brahim; Mariem Youssouf Issa; Mohamed Lemine Zamel; Sarah Montesdeoca-Esponda (Biological Trace Element Research, 2023)
In Mauritania, the dromedary breeding is the most widespread pastoral activity, and it is considered as the first source of animal protein; however, the research on meat is relatively rare compared with fish, especially in relation with the presence of trace metals. In this work, livers, kidneys, and muscles of 25 Camelus dromedarius were collected from butcheries in Nouakchott (Mauritania) between February and April 2020 to study the concentration of trace metals (three essential metals: cooper (Cu), iron (Fe), and zinc (Zn), and four toxic metals: mercury (Hg), arsenic (As), cadmium (Cd), and lead (Pb)). Statistical treatment did not show significant differences associated with age ( P = 0.7004), sex ( P = 0.9353), or type of diet (0.9951) in the found concentration of the target substances, but the differences were significant between metals and between organs ( P < 0.0001). The mean concentrations of the essential metals were 0.80 mg/100 g for Cu, 6.02 mg/100 g for Fe, and 3.28 mg/100 g for Zn, and the ratios between these concentrations were significant ( P < 0.0001 in all cases), with [Fe] > [Zn] > [Cu]. Cu was most concentrated in the liver, Fe in the kidney, and Zn in muscle. The mean concentrations of toxic metals were 0.055 mg/kg for As, 0.064 mg/kg for Cd, 0.040 mg/kg for Pb, and 0.027 mg/kg for Hg. They also exhibited significant difference between organs. Hg and Pb showed their largest concentrations in the liver, whereas As and Cd reached their maximum values in the kidney. Therefore, the found concentrations in all cases were lower than the admissible level of trace metals.

The Yellow-breasted Barbet (Trachyphonus margaritatus) introduces vocal duets and choruses with a specific multimodal signal, during territorial advertisement - Mathieu Mahamoud Issa; Bożena Sikora; Stanisław Rusiecki; Tomasz S. Osiejuk (Journal of Ornithology, 2023)
Cooperative behaviour is a prominent feature among many group-living species and continues to pose challenges to our understanding about the evolution of social relationships and task coordination between members of the same social group. Individuals who are willing to cooperate to achieve a joined action need to communicate their intentions and somehow make a common agreement. We investigated how a coordinated chorus song is initiated in a cooperative-breeding bird species, The Yellow-Breasted Barbet ( Trachyphonus margaritatus ). A chorus can be defined as an interactive vocal display involving several individuals who are synchronizing their behaviour to sing in a time coordinated manner. Synchronizing behaviour to sing in chorus might become quite challenging when several individuals are involved. Thus, group members could use a specific signal to induce such collective action. Yet, few studies have investigated the mechanisms of communal display initiation in chorusing bird species. We conducted playback experiments to induce and record territorial defensive reactions from birds with a video camera. We recorded 26 different groups from distinct wild populations in Djibouti which belonged to 17 sites. We found that barbets use a specific vocalization named chewp note to introduce their duet and chorus. Moreover, we found that the individual that initiates such communal displays may broadcast a multimodal signal by combining chewp note series with a typical body posture with the tail raised and fanned. We suggest that the multimodal signal could serve to attract attention and elicit a response from other group members or could enhance the song coordination.

Late Pleistocene travertine deposits in the Jordan Valley—Dead Sea area: lithofacies, sedimentological properties and depositional environments - Issa M. Makhlouf; Khalil M. Ibrahim; Ali R. El Naqah; Sana’ M. Al-Thawabteh (Arabian Journal of Geosciences, 2023)

Designating the First Vernal Pool Micro-Reserve in a Buffer Zone of Wadi Qana Protected Area, Palestine - Mazin B. Qumsiyeh; Elias N. Handal; Banan Al-Sheikh; Mohammad H. Najajreh; Issa Musa Albaradeiya (Wetlands, 2022)

Taurine mitigates the development of pulmonary inflammation, oxidative stress, and histopathological alterations in a rat model of bile duct ligation - Mohammad Mehdi Ommati; Ali Mobasheri; Yanqin Ma; Dongmei Xu; Zhongwei Tang; Ram Kumar Manthari; Narges Abdoli; Negar Azarpira; Yu Lu; Issa Sadeghian; Abolghasem Mousavifaraz; Ali Nadgaran; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

The role of ivabradine in doxorubicin-induced cardiotoxicity: exploring of underlying argument - Hayder M. Al-kuraishy; Hajer K. Issa; Ali I. Al-Gareeb; Maisra M. El-Bouseary; Amal Youssef; Ahmed Shaban Abdelaziz; Hesham Ahmed Khalifa; Gaber El-Saber Batiha (Inflammopharmacology, 2022)

Ecofriendly adsorption and sensitive detection of Hg (II) by biomass-derived nitrogen-doped carbon dots: process modelling using central composite design - Mohammed Abdullah Issa; Hamid Zentou; Zaid H. Jabbar; Zurina Z. Abidin; Haninah Harun; Noor Amirah Abdul Halim; Mohammed M. Alkhabet; Musa Y. Pudza (Environmental Science and Pollution Research, 2022)

The potential of endophytic bacteria from Prosopis cineraria for the control of Pythium aphanidermatum-induced damping-off in cucumber under saline water irrigation - Ahad Al-Rashdi; Fatma Sulaiman Al-Hinai; Majida Mohammed Ali Al-Harrasi; Jamal Nasser Al-Sabahi; Rahil Said Al-Badi; Issa Hashil Al-Mahmooli; Abdullah Mohammed Al-Sadi; Rethinasamy Velazhahan (Journal of Plant Pathology, 2022)

Hexamermis sp. a potential candidate for the biological control of the fall armyworm in two agroecological zones of Senegal - Amadou Balde; Serigne Sylla; Etienne Tendeng; Babacar Labou; Mamadou Diatte; Oumar Seydi; Issa Alé Ndiaye; Serigne Omar Sene; Pape Diop; Karamoko Diarra (Phytoparasitica, 2022)

Surface circulation properties in the eastern Mediterranean emphasized using machine learning methods - Georges Baaklini; Roy El Hourany; Milad Fakhri; Julien Brajard; Leila Issa; Gina Fifani; Laurent Mortier (Ocean Science, 2022)
The eastern Mediterranean surface circulation is highly energetic and composed of structures interacting stochastically. However, some main features are still debated, and the behavior of some fine-scale dynamics and their role in shaping the general circulation is yet unknown. In the following paper, we use an unsupervised neural network clustering method to analyze the long-term variability of the different mesoscale structures. We decompose 26 years of altimetric data into clusters reflecting different circulation patterns of weak and strong flows with either strain or vortex-dominated velocities. The vortex-dominated cluster is more persistent in the western part of the basin, which is more active than the eastern part due to the strong flow along the coast, interacting with the extended bathymetry and engendering continuous instabilities. The cluster that reflects a weak flow dominated the middle of the basin, including the Mid-Mediterranean Jet (MMJ) pathway. However, the temporal analysis shows a frequent and intermittent occurrence of a strong flow in the middle of the basin, which could explain the previous contradictory assessment of MMJ existence using in-situ observations. Moreover, we prove that the Levantine Sea is becoming more and more energetic as the activity of the main mesoscale features is showing a positive trend.

Evaluation of Coupled Interaction Effects Caused by the Long-Term Performance of Energy Piles in a Piled Raft Foundation - Hassan Abbaszadeh Amirdehi; Issa Shooshpasha (Geotechnical and Geological Engineering, 2022)

Enhancement of yield through marker-assisted pyramiding of yield contributing genes in rice (Oryza sativa L.) var. BPT5204 - Syamala Pulindala; Reddyyamini Bommisetty; Darsha Manjula Withanawasam; Sasikala Somagutta; Madhavilatha Kommana; Sudhamani Kalluru; Issa Keerthi; Sreelakshmi Chintala; Lakshminarayana R. Vemireddy (Euphytica, 2022)

Sea level rise and future shoreline changes along the sandy coast of Saloum Delta, Senegal - Issa Sakho; Mamadou Sadio; Ibrahima Camara; Mélinda Noblet; Aïchetou Seck; Cherdvong Saengsupavanich; Abdoulaye Ndour; Mouhamadoul Bachir Diouf (Arabian Journal of Geosciences, 2022)

Moving Experience from North America to Developing Country to Approach a Desired Level of Quality Assurance in Head and Neck Radiation Therapy - Issa Mohamad; Ali Hosni; Ramiz Abu-Hijlih; Abdellatif Al Mousa; Dalia Al-Rimawi; Fawzi Abuhijla (Journal of Cancer Education, 2022)

Stories of change in nutrition in Burkina Faso 1992–2018: a micro-level perspective - Elodie Becquey; Issa Sombié; Mariama Touré; Zuzanna Turowska; Emilie Buttarelli; Nicholas Nisbett (Food Security, 2022)
Looking back at what has effectively improved nutrition may inform policy makers on how to accelerate progress to end all forms of malnutrition by 2030. As under-five stunting declined substantially in Burkina Faso, we analyzed its nutrition story at the micro-level. We conducted a regression-decomposition analysis to identify demographic and health drivers associated with change in height-for-age using longitudinal, secondary, nationally-representative data. We triangulated results with findings from semi-structured community interviews (n = 91) in two “model communities” with a history of large stunting reduction. We found that improvement in immunization coverage, assets accumulation and reduction in open defecation were associated with 23%, 10% and 6.1% of the improvement in height-for-age, respectively. Associations were also found with other education, family planning, health and WASH indicators. Model communities acknowledged progress in the coverage and quality of nutrition-specific and nutrition-sensitive sectoral programs co-located at the community level, especially those delivered through the health and food security sectors, though delivery challenges remained in a context of systemic poverty and persistent food insecurity. Burkina Faso’s health sector’s success in improving coverage of nutrition and healthcare programs may have contributed to improvements in child nutrition alongside other programmatic improvements in the food security, WASH and education sectors. Burkina Faso should continue to operationalize sectoral nutrition-sensitive policies into higher-quality programs at scale, building on its success stories such as vaccination. Community leverage gaps and data gaps need to be filled urgently to pressure for and monitor high coverage, quality delivery, and nutrition impact of agriculture, education, and WASH interventions.

Potential of ( Citrus nobilis Lour × Citrus deliciosa Tenora) metabolites on COVID-19 virus main protease supported by in silico analysis - Seham S. El-Hawary; Marwa Y. Issa; Hanaa S. Ebrahim; Anber F. Mohammed; Alaa M. Hayallah; Essam M. Abd El-Kadder; Ahmed. M. Sayed; Usama Ramadan Abdelmohsen (Natural Product Research, 2022)

The potential for acoustic individual identification in mammals - Pavel Linhart; Mathieu Mahamoud-Issa; Dan Stowell; Daniel T. Blumstein (Mammalian Biology, 2022)

AnMBR technology for landfill leachate treatment: a framework towards improved performance - Lea Issa; Olga El Kik; Mutasem El-Fadel (Reviews in Environmental Science and Bio/Technology, 2022)

Bioactive phenolic components and antioxidant activities of water-based extracts and flavonoid-rich fractions from Salvadora persica L. leaves - Issa Issoufou Ibrahim; Ag Arya Moussa; Zhuo Chen; Jun Zhang; Wei-Guo Cao; Chao Yu (Natural Product Research, 2022)

ICP-MS determination of elemental abundance in traditional medicinal plants commonly used in the Kingdom of Saudi Arabia - Rizwan Ahmad; Heba Shaaban; Sahar Y. Issa; Anwar Alsaad; Majd Alghamdi; Njoud Hamid; Rand Osama; Sara Algarni; Ahmed Mostafa; Abdulmalik M. Alqarni; Mohammed Aldholmi; Muhammad Riaz (Food Additives & Contaminants Part B-Surveillance, 2022)

Reverse orientation in the ultrasound-assisted [3 + 2]-cycloaddition reaction of nitrile imines with 3-formylchromone-Meldrum’s acid adducts - Issa Yavari; Younes Fadakar (Molecular Diversity, 2022)

TFA-mediated synthesis of functionalized pyrano[2,3-c]pyrazoles from pyrazol-3-ones, active carbonyl compounds and tert-BuOH - Issa Yavari; Jamil Sheykhahmadi (Molecular Diversity, 2022)

Impact of COVID-19 pandemic on aircraft noise levels, annoyance, and health effects in an urban area in Oman - Patrick Amoatey; Issa Al-Harthy; Khalifa Al-Jabri; Abdullah Al-Mamun; Mahad Said Baawain; Ahmed Al-Mayahi (Environmental Science and Pollution Research, 2022)

Deposition Modeling of Airborne Particulate Matter on Human Respiratory Tract During Winter Seasons in Arid-Urban Environment - Patrick Amoatey; Hamid Omidvarborna; Khalifa Al-Jabri; Issa Al-Harthy; Mahad Said Baawain; Abdullah Al-Mamun (Aerosol Science and Engineering, 2022)

Effect of ambient noise on indoor environments in a health care facility in Oman - Patrick Amoatey; Issa Al-Harthy; Muntasar Ali Al-Mushaifari; Khalifa Al-Jabri; Abdullah Al-Mamun (Environmental Science and Pollution Research, 2022)

Assessing the influence of integrating soil amendment applications with saline water irrigation on Ajwain’s yield and water productivity - Mahdi Kalanaki; Fatemeh Karandish; Payman Afrasiab; Henk Ritzema; Issa Khamari; Seyed Mahmood Tabatabai (Irrigation Science, 2022)

Mechanisms of COVID-19-induced kidney injury and current pharmacotherapies - Wissam H. Faour; Ali Choaib; Elio Issa; Francesca El Choueiry; Khodor Shbaklo; Maryline Alhajj; Ramy Touma Sawaya; Zeina Harhous; Eman Alefishat; Moni Nader (Inflammation Research, 2022)
The COVID-19 pandemic created a worldwide debilitating health crisis with the entire humanity suffering from the deleterious effects associated with the high infectivity and mortality rates. While significant evidence is currently available online and targets various aspects of the disease, both inflammatory and noninflammatory kidney manifestations secondary to COVID-19 infection are still largely underrepresented. In this review, we summarized current knowledge about COVID-19-related kidney manifestations, their pathologic mechanisms as well as various pharmacotherapies used to treat patients with COVID-19. We also shed light on the effect of these medications on kidney functions that can further enhance renal damage secondary to the illness.

Influences of silica fume particles and polyethylene terephthalate fibers on the mechanical characteristics of cement-treated sandy soil using ultrasonic pulse velocity - Ali Hasanzadeh; Issa Shooshpasha (Bulletin of Engineering Geology and the Environment, 2022)

Comparative Rodenticide Activity of Three Agro Waste Materials in Combat of Rattus norvegicus Under Laboratory Conditions - Marwa Y. Issa; Walaa S. Nasser; Micheal William Mikhail; Essam Abdel-Sattar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Environmental monitoring and assessment: a case in Salalah, Oman - Mahaad Issa Shammas (Environmental Monitoring and Assessment, 2021)

Integrating international linguistic minorities in emergency planning at institutions of higher education - Amer Hamad Issa Abukhalaf; Jason von Meding (Natural Hazards, 2021)

Seismic and earthquake engineering studies in the Arabian plate and the surrounding region - Issa El-Hussain; Ahmed Deif; Rengin Gok; Keith Nakanishi (Arabian Journal of Geosciences, 2021)

Assessment of noise levels and induced annoyance in nearby residential areas of an airport region in Oman - Issa Al-Harthy; Patrick Amoatey; Abdullah Al-Mamun; Zahir Alabri; Mahad Said Baawain (Environmental Science and Pollution Research, 2021)

Artificial reproduction and reproductive parameters of silver catfish Schilbe intermedius (Siluriformes: Schilbeidae) – implications for the conservation and domestication of this threatened species - Comlan Ephrem Tossavi; Nahoua Issa Ouattara; Emile Didier Fiogbe; Jean-Claude Micha (Biologia, 2021)

Characterization and exposure assessment to urban air toxics across Middle Eastern and North African countries: a review - Patrick Amoatey; Ahmed Al-Mayahi; Issa Al-Harthy; Khalifa Al-Jabri; Maxwell Nana Addi; Sajjad Ahmad Siddiqi; Hameed Sulaiman; Abdullah Al-Mamun; Mahad Said Baawain (Environmental Monitoring and Assessment, 2021)

Integrating seasonal climate forecasts into adaptive social protection in the Sahel - Joseph Daron; Mary Allen; Meghan Bailey; Luisa Ciampi; Rosalind Cornforth; Cecilia Costella; Nicolas Fournier; Richard Graham; Kathrin Hall; Cheikh Kane; Issa Lele; Celia Petty; et al. (Climate and Development, 2021)

Beat the stress: breeding for climate resilience in maize for the tropical rainfed environments - Boddupalli M. Prasanna; Jill E. Cairns; P. H. Zaidi; Yoseph Beyene; Dan Makumbi; Manje Gowda; Cosmos Magorokosho; Mainassara Zaman-Allah; Mike Olsen; Aparna Das; Mosisa Worku; James Gethi; et al. (Theoretical and Applied Genetics, 2021)
Key message Intensive public sector breeding efforts and public-private partnerships have led to the increase in genetic gains, and deployment of elite climate-resilient maize cultivars for the stress-prone environments in the tropics. Abstract Maize ( Zea mays L.) plays a critical role in ensuring food and nutritional security, and livelihoods of millions of resource-constrained smallholders. However, maize yields in the tropical rainfed environments are now increasingly vulnerable to various climate-induced stresses, especially drought, heat, waterlogging, salinity, cold, diseases, and insect pests, which often come in combinations to severely impact maize crops. The International Maize and Wheat Improvement Center (CIMMYT), in partnership with several public and private sector institutions, has been intensively engaged over the last four decades in breeding elite tropical maize germplasm with tolerance to key abiotic and biotic stresses, using an extensive managed stress screening network and on-farm testing system. This has led to the successful development and deployment of an array of elite stress-tolerant maize cultivars across sub-Saharan Africa, Asia, and Latin America. Further increasing genetic gains in the tropical maize breeding programs demands judicious integration of doubled haploidy, high-throughput and precise phenotyping, genomics-assisted breeding, breeding data management, and more effective decision support tools. Multi-institutional efforts, especially public–private alliances, are key to ensure that the improved maize varieties effectively reach the climate-vulnerable farming communities in the tropics, including accelerated replacement of old/obsolete varieties.

Fibroblast Growth Factor 9 Stimulates Neuronal Length Through NF-kB Signaling in Striatal Cell Huntington’s Disease Models - Issa Olakunle Yusuf; Hsiu-Mei Chen; Pei-Hsun Cheng; Chih-Yi Chang; Shaw-Jenq Tsai; Jih-Ing Chuang; Chia-Ching Wu; Bu-Miin Huang; H. Sunny Sun; Chuan-Mu Chen; Shang-Hsun Yang (Molecular Neurobiology, 2021)

Synthesis of thia- and thioxo-tetraazaspiro[4.4]nonenones from nitrile imines and arylidenethiohydantoins - Issa Yavari; Zohreh Taheri; Sara Sheikhi; Samira Bahemmat; Mohammad R. Halvagar (Molecular Diversity, 2021)

Improved lithospheric attenuation structure of the Arabian Peninsula through the use of national network data - Michael E. Pasyanos; Yahya M. Tarabulsi; Salah Y. Al-Hadidy; Wael W. Raddadi; Abdullah D. Mousa; Issa El-Hussain; Farah Al-Jeri; Haydar Al-Shukri; Rengin Gök (Arabian Journal of Geosciences, 2021)

Site-specific deterministic and probabilistic tsunami hazard assessment for Diba-Oman and Diba-Al-Emirates - Issa El-Hussain; Zaid Al-Habsi; Khalid Al Bloushi; Rachid Omira; Ahmed Deif; Maria Ana Baptista; Adel M. E. Mohamad (Arabian Journal of Geosciences, 2021)

Artificial Reproduction and Embryogeny of the Tiger Frog Hoplobatrachus occipitalis (Günther 1858) - Théophile Godome; Sèlomè Wilfried Sintondji; Mahunan Tobias Césaire Azon; Comlan Ephrem Tossavi; Nahoua Issa Ouattara; Emile Didier Fiogbe (Proceedings of the Zoological Society, 2021)

Co-circulation of genotypes XIV.2 and XVIII.2 of avian paramyxovirus-1 (Newcastle disease virus) in backyard poultry in Niger - Maman Moutari Souley; Abdoulkarim Issa Ibrahim; Bachir Souley Kouato; Alassane Abdou; Rahila Issa; Bachir Yaou; Hadiza Amadou; Hama Hama; Hassane Adakal; Nourou Abdou; Giovanni Cattoli; William G. Dundon (Virus Genes, 2021)

Exploratory Study on Lercanidipine Hydrochloride Polymorphism: pH-Dependent Solubility Behavior and Simulation of its Impact on Pharmacokinetics - Ilia Alekseevich Repin; Raimar Loebenberg; John DiBella; António C. L. Conceição; Manuel E. Minas da Piedade; Humberto G. Ferraz; Michele G. Issa; Nadia A. Bou-Chacra; Catharine F. M. Ermida; Gabriel L. B. de Araujo (AAPS PharmSciTech, 2021)

A literature-based study on the water–energy–food nexus for sustainable development - José Baltazar Salgueirinho Osório de Andrade Guerra; Issa Ibrahim Berchin; Jessica Garcia; Samara da Silva Neiva; Ana Valquiria Jonck; Rafael Avila Faraco; Wellyngton Silva de Amorim; João Marcelo Pereira Ribeiro (Stochastic Environmental Research and Risk Assessment, 2021)

Evaluation of the seismic response of the slopes in the presence of the horseshoe tunnel - Hadi Mashhadban; Asskar Janalizadeh Choobbasti; Issa Shooshpasha; Mehdi Ashtiani (Bulletin of Engineering Geology and the Environment, 2021)

Assessment of Agro-morphological Performances of 56 Accessions of Pennisetum glaucum with Grain and Fodder Potentials in Niger - Hamadou Moussa; Valentin Kindomihou; Thierry D. Houehanou; Mahamadou Chaibou; Oumarou Souleymane; Idrissa Soumana; Salissou Issa; Ahmadou Issaka; Kassari Ango Issoufou; Joseph Dossou; Frédéric Houndonougbo; Sévérin Babatoundé; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Production of antifungal metabolites by the antagonistic bacterial isolate Pseudomonas resinovorans B11 - Dhuha Sulaiman Salim Al-Daghari; Issa Hashil Al-Mahmooli; Abdullah Mohammed Al-Sadi; Jamal Nasser Al-Sabahi; Rethinasamy Velazhahan (Indian Phytopathology, 2020)

Influence of Silica Fume on the Geotechnical Characteristics of Cemented Sand - Ali Hasanzadeh; Issa Shooshpasha (Geotechnical and Geological Engineering, 2020)

Physicochemical Changes of Surimi Gels with Addition of Different Particle Sizes of Citrus Peel Fiber - Abdulhakim Sharaf Eddin; Samuel Adegoke; Aseel T. Issa; Cassidy Wilson; Reza Tahergorabi (Journal of Aquatic Food Product Technology, 2020)

Sanitary quality improvement of fish produced in the northern Benin cotton basin water reservoirs by cage culture and fish transfer in agricultural contaminant-free water: human health implications - Rodrigue O. E. Pèlèbè; Ibrahim Imorou Toko; Issa N. Ouattara; Ulbad P. Tougan; Eloi Y. Attakpa; Jean Fall; Elie Montchowui (Tropical Animal Health and Production, 2020)

Communication challenges in campus emergency planning: the case of Hurricane Dorian in Florida - Amer Hamad Issa Abukhalaf; Jason von Meding (Natural Hazards, 2020)

Discovery of genomic regions and candidate genes for grain weight employing next generation sequencing based QTL-seq approach in rice (Oryza sativa L.) - Reddyyamini Bommisetty; Navajeet Chakravartty; Reddaiah Bodanapu; Jeevula B. Naik; Sanjib K. Panda; Sivarama P. Lekkala; Krishna Lalam; George Thomas; S. J. Mallikarjuna; G. R. Eswar; Gopalakrishna M. Kadambari; Swarajyalakshmi N. Bollineni; et al. (Molecular Biology Reports, 2020)

Exposure assessment to road traffic noise levels and health effects in an arid urban area - Patrick Amoatey; Hamid Omidvarbona; Mahad Said Baawain; Ahmed Al-Mayahi; Abdullah Al-Mamun; Issa Al-Harthy (Environmental Science and Pollution Research, 2020)

Seismic monitoring and high-frequency noise using arrays in the Arabian Peninsula - Moira L. Pyle; Rengin Gök; Abdullah Al-Amri; Issa El-Hussain; Yasir Al-Rawahi (Arabian Journal of Geosciences, 2020)

The pervasive and multifaceted influence of biocrusts on water in the world's drylands - David J. Eldridge; Sasha Reed; Samantha K. Travers; Matthew A. Bowker; Fernando T. Maestre; Jingyi Ding; Caroline Havrilla; Emilio Rodriguez‐Caballero; Nichole Barger; Bettina Weber; Anita Antoninka; Jayne Belnap; et al. (Global Change Biology, 2020)
The capture and use of water are critically important in drylands, which collectively constitute Earth's largest biome. Drylands will likely experience lower and more unreliable rainfall as climatic conditions change over the next century. Dryland soils support a rich community of microphytic organisms (biocrusts), which are critically important because they regulate the delivery and retention of water. Yet despite their hydrological significance, a global synthesis of their effects on hydrology is lacking. We synthesized 2,997 observations from 109 publications to explore how biocrusts affected five hydrological processes (times to ponding and runoff, early [sorptivity] and final [infiltration] stages of water flow into soil, and the rate or volume of runoff) and two hydrological outcomes (moisture storage, sediment production). We found that increasing biocrust cover reduced the time for water to pond on the surface (−40%) and commence runoff (−33%), and reduced infiltration (−34%) and sediment production (−68%). Greater biocrust cover had no significant effect on sorptivity or runoff rate/amount, but increased moisture storage (+14%). Infiltration declined most (−56%) at fine scales, and moisture storage was greatest (+36%) at large scales. Effects of biocrust type (cyanobacteria, lichen, moss, mixed), soil texture (sand, loam, clay), and climatic zone (arid, semiarid, dry subhumid) were nuanced. Our synthesis provides novel insights into the magnitude, processes, and contexts of biocrust effects in drylands. This information is critical to improve our capacity to manage dwindling dryland water supplies as Earth becomes hotter and drier.

Utilization of Thinned Sunflower and Soybean Intercrops as Forage: A Useful Strategy for Small Scale Farms in Intensive Agricultural Systems - Heba Sabry Attia Salama; Hassan El-Sayed Khalil; Ali Issa Nawar (International Journal of Plant Production, 2020)

Probability of magnitude detection for the seismological network of Oman - Issa El-Hussain; Mohamed Ezzelarab; Mahmoud Sami Soliman; Ahmed Deif; Adel Mohamed El-Shahat Mohamed (Arabian Journal of Geosciences, 2020)

A synthesis of N-(1H-pyrazol-5-yl)-1,3,4-thiadiazol-2(3H)-imines from nitrile imines and Erlenmeyer thioazlactones - Issa Yavari; Zohreh Taheri; Sara Sheikhi; Samira Bahemmat; Mohammad R. Halvagar (Molecular Diversity, 2020)

Study of the 24 September 2013 Oman Sea tsunami using linear shallow water inversion - Maria Ana Baptista; Jorge Miguel Miranda; Rachid Omira; Issa El-Hussain (Arabian Journal of Geosciences, 2020)

Updating a probabilistic seismic hazard model for Sultanate of Oman - Ahmed Deif; Issa El-Hussain; Yousuf Alshijbi; Adel Mohamed El-Shahat Mohamed (Arabian Journal of Geosciences, 2020)

Kamerabasiertes Durchflussmess-verfahren an Fließgewässern - Fallstudie Peißenberg-Hochwasser Mai 2019 - Issa Hansen; Karlheinz Daamen; Salvador Peña-Haro (WASSERWIRTSCHAFT, 2020)

Anticoccidial effects of Khaya senegalensis aqueous stem bark extract on broiler chickens experimentally infected with Eimeria species - Issa A. Muraina; Jurbe G. Gotep; James T. Tanko; ThankGod E. Onyiche; Oladimeji B. Aladelokun; Christiana C. Dapuliga; Gilead E. Forcados; Nonyelim Ozele; Ann L. Samuel; Olusola O. Oladipo; Olatunde B. Akanbi; Philip A. Okewole; et al. (Tropical Animal Health and Production, 2020)

Translational genomics for achieving higher genetic gains in groundnut - Manish K. Pandey; Arun K. Pandey; Rakesh Kumar; Chogozie Victor Nwosu; Baozhu Guo; Graeme C. Wright; Ramesh S. Bhat; Xiaoping Chen; Sandip K. Bera; Mei Yuan; Huifang Jiang; Issa Faye; et al. (Theoretical and Applied Genetics, 2020)
Key message Groundnut has entered now in post-genome era enriched with optimum genomic and genetic resources to facilitate faster trait dissection, gene discovery and accelerated genetic improvement for developing climate-smart varieties. Abstract Cultivated groundnut or peanut ( Arachis hypogaea ), an allopolyploid oilseed crop with a large and complex genome, is one of the most nutritious food. This crop is grown in more than 100 countries, and the low productivity has remained the biggest challenge in the semiarid tropics. Recently, the groundnut research community has witnessed fast progress and achieved several key milestones in genomics research including genome sequence assemblies of wild diploid progenitors, wild tetraploid and both the subspecies of cultivated tetraploids, resequencing of diverse germplasm lines, genome-wide transcriptome atlas and cost-effective high and low-density genotyping assays. These genomic resources have enabled high-resolution trait mapping by using germplasm diversity panels and multi-parent genetic populations leading to precise gene discovery and diagnostic marker development. Furthermore, development and deployment of diagnostic markers have facilitated screening early generation populations as well as marker-assisted backcrossing breeding leading to development and commercialization of some molecular breeding products in groundnut. Several new genomics applications/technologies such as genomic selection, speed breeding, mid-density genotyping assay and genome editing are in pipeline. The integration of these new technologies hold great promise for developing climate-smart, high yielding and more nutritious groundnut varieties in the post-genome era.

Efficacy of native antagonistic rhizobacteria in the biological control of Pythium aphanidermatum-induced damping-off of cucumber in Oman - Dhuha Sulaiman Salim Al-Daghari; Shurooq Abdullah Al-Abri; Issa Hashil Al-Mahmooli; Abdullah Mohammed Al-Sadi; Rethinasamy Velazhahan (Journal of Plant Pathology, 2020)

Biofilms grown in aquatic microcosms affect mercury and selenium accumulation in Daphnia - Semona Issa; Tomasz Maciej Ciesielski; Øyvind Mikkelsen; Sigurd Einum; Veerle L. B. Jaspers (Ecotoxicology, 2020)
Experiments examining mercury (Hg) toxicity in Daphnia are usually conducted in highly standardized conditions that prevent the formation of biofilm. Although such standardization has many advantages, extrapolation of results to natural conditions and inference of ecological effects is challenging. This is especially true since biofilms can accumulate metals/metalloids and play a key role in their transfer to higher trophic level organisms. In this study, we experimentally tested the effects of spontaneously appearing biofilm in Daphnia cultures on accumulation of Hg and its natural antagonist selenium (Se) in Daphnia magna . We added Hg (in the form of mercury (II) chloride) at two concentrations (0.2 µg/L and 2 µg/L) to experimental microcosms and measured the uptake of Hg and Se by D. magna in the presence and absence of biofilm. To test for consistent and replicable results, we ran two identical experimental sets one week apart. Biofilm presence significantly reduced the accumulation of Hg, while increasing the tissue Se content in D. magna , and these findings were reproducible across experimental sets. These findings indicate that highly standardized tests may not be adequate to predict the bioaccumulation and potential toxicity of metals/metalloids under natural conditions.

Evaluation of ground dynamic characteristics using ambient noise measurements in a landslide area - Sadegh Rezaei; Issa Shooshpasha; Hamed Rezaei (Bulletin of Engineering Geology and the Environment, 2020)

Impacts of a nonwoven geotextile arrangement on load-bearing capacity of reinforced sand: a laboratory study - Yashar Tavangar; Issa Shooshpasha (Innovative Infrastructure Solutions, 2020)

Myocardial adaptability in young and older-aged sea-level habitants sojourning at Mt Kilimanjaro: are cardiac compensatory limits reached in older trekkers? - Glenn M. Stewart; Courtney M. Wheatley-Guy; Norman R. Morris; Kirsten E. Coffman; Jan Stepanek; Alex R. Carlson; Amine Issa; Michael A. Schmidt; Bruce D. Johnson (European Journal of Applied Physiology, 2020)

Structure of benthic macroinvertebrates population in an area of Mopoyem Bay (Ebrie Lagoon, Côte d’Ivoire) exposed to the discharge of a fish farm effluents - Kouamé Parfait Yoboué; Nahoua Issa Ouattara; Siaka Berté; Benié Rose Danielle Aboua; Julien Kalpy Coulibaly; Essetchi Paul Kouamélan (Environmental Monitoring and Assessment, 2020)

Biomaterials for orthopedics: anti-biofilm activity of a new bioactive glass coating on titanium implants - Daniella Maia Marques; Viviane de Cássia Oliveira; Marina Trevelin Souza; Edgar Dutra Zanotto; João Paulo Mardegan Issa; Evandro Watanabe (Biofouling, 2020)

Genetic polymorphism of drug metabolism enzymes (GSTM1, GSTT1 and GSTP1) in the healthy Malian population - Yaya Kassogue; Brehima Diakite; Oumar Kassogue; Issa Konate; Kadidiatou Tamboura; Zoumana Diarra; Hind Dehbi; Sellama Nadifi; Cheick Bougadari Traore; Sounkalo Dao; Seydou Doumbia; Guimogo Dolo (Molecular Biology Reports, 2020)
Glutathione S-transferase genes, known to be highly polymorphic, are implicated in the process of phase II metabolism of many substrates, including xenobiotics, anticancer and anti-infective drugs. The detoxification activity is linked to individual genetic makeup. Therefore, the identification of alleles and genotypes in these genes within a population may help to better design genetic susceptibility and pharmacogenetic studies. We performed the present study to establish the frequencies of the GSTM1 , GSTT1 , and GSTP1 c. 313A > G (rs1695) polymorphisms in 206 individuals of the Malian healthy population. GSTM1 and GSTT1 were genotyped by using multiplex polymerase chain reaction, whereas genotypes of GSTP1 were identified by polymerase chain reaction followed by restriction fragment length polymorphism. The frequencies of GSTM1 -null and GSTT1 -null genotypes were respectively 24.3 and 41.3%. The observed genotype frequencies for GSTP1 were 25.73% homozygous wild-type AA, 49.03% heterozygous AG and 25.24% homozygous mutant GG. The frequency of GSTP1 -A allele was 50.24% versus 49.76% for the GSTP1 - G allele . The distribution of these three genes was homogeneous between men and women (p > 0.05). We found no statistical association between the presence of a particular profile of GSTM1 or GSTT1 with the genotypes of GSTP1 ( p > 0.05). Nevertheless, we noticed that the majority of the individuals harboring the GSTM1 -present or the GSTT1 -present harbor also the GSTP1 -AG genotype. In addition, the triple genotype GSTM1 -present/ GSTT1 -present/AG was the most frequent with 25.2%. Our findings will facilitate future studies regarding genetic associations of multifactorial diseases and pharmacogenetic, thus opening the way to personalized medicine in our population.

Serum agrin and talin are increased in major depression while agrin and creatine phosphokinase are associated with chronic fatigue and fibromyalgia symptoms in depression - Hussein Kadhem Al-Hakeim; Ameer Abdul Razzaq Al-Issa; Michael Maes (Metabolic Brain Disease, 2020)

Berührlose optische Durchflussmessung unter hochalpinen Verhältnissen - Maxence Carrel; Salvador Peña-Haro; Beat Luethi; Issa Hansen (WASSERWIRTSCHAFT, 2019)

Crystal structure and configuration revision of 9-hydroxy-7,8-dehydro-sarcotrocheliol and sarcotrocheliol - Abdelaaty Hamed; Marwa Y. Issa; Mohamed A. Ghani; Marcel Frese; Beate Neumann; Hans Georg Stammler; Norbert Sewald; Mohamed Shaaban (Natural Product Research, 2019)

Carbon stock assessment of date palm using remote sensing coupled with field-based measurements in Abu Dhabi (United Arab Emirates) - Salem Issa; Basam Dahy; Nazmi Saleous; Taoufik Ksiksi (International Journal of Remote Sensing, 2019)

Appraisal of immediate and late effects of mobile phone radiations at 2100 MHz on mitotic activity and DNA integrity in root meristems of Allium cepa - Shikha Chandel; Shalinder Kaur; Mohd Issa; Harminder Pal Singh; Daizy Rani Batish; Ravinder Kumar Kohli (Protoplasma, 2019)

The potential role of angiopoietin-like protein-8 in type 2 diabetes mellitus: a possibility for predictive diagnosis and targeted preventive measures? - Yasmine Amr Issa; Samar Samy Abd ElHafeez; Noha Gaber Amin (EPMA Journal, 2019)

What is the time-to-positivity of blood cultures in infective endocarditis? - Olivia Peuchant; Nahéma Issa; Irène Machelart; Carine Greib; Gaetane Wirth; Fabrice Camou (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Author Correction: Aging and Nutrition: Theories, Consequences, and Impact of Nutrients - Nassifatou Koko Tittikpina; Abdul-raouf Issa; Mouhoudine Yerima; Affo Dermane; Sika Dossim; Mounerou Salou; Batomayena Bakoma; Aboudoulatif Diallo; Yao Potchoo; Yerim Mbagnick Diop (Current Pharmacology Reports, 2019)

Aging and Nutrition: Theories, Consequences, and Impact of Nutrients - Nassifatou Koko Tittikpina; Abdul-raouf Issa; Mouhoudine Yerima; Affo Dermane; Sika Dossim; Mounerou Salou; Batobayena Bakoma; Aboudoulatif Diallo; Yao Potchoo; Yerim Mbagnick Diop (Current Pharmacology Reports, 2019)

Chironomus sancticaroli (Diptera, Chironomidae) as a Sensitive Test Species: Can We Rely on Its Use After Repeated Generations, Under Laboratory Conditions? - Juliano J. Corbi; Aline C. Bernegossi; Lidia Moura; Mayara C. Felipe; Carina G. Issa; Mara Rubia L. Silva; Guilherme R. Gorni (Bulletin of Environmental Contamination and Toxicology, 2019)

Kamerabasierte Durchflussmessung in offenen Kanälen und Flüssen - Issa Hansen; Christian Satzger; Beat Lüthi; Salvador Peña-Haro (WASSERWIRTSCHAFT, 2019)

Deaggregation of probabilistic seismic hazard for selected cities in the Arabian Peninsula - Yousuf Al-Shijbi; Ahmed Deif; Issa El-Hussain; Adel M. E. Mohamed; Amna Al-Dairi (Arabian Journal of Geosciences, 2019)

Reconstruction of landslide model from ERT, geotechnical, and field data, Nargeschal landslide, Iran - Sadegh Rezaei; Issa Shooshpasha; Hamed Rezaei (Bulletin of Engineering Geology and the Environment, 2019)

Exposure to mobile phone radiations at 2350 MHz incites cyto- and genotoxic effects in root meristems of Allium cepa - Shikha Chandel; Shalinder Kaur; Mohd Issa; Harminder Pal Singh; Daizy Rani Batish; Ravinder Kumar Kohli (Journal of Environmental Health Science and Engineering, 2019)

Biological control of damping-off of tomato caused by Pythium aphanidermatum by using native antagonistic rhizobacteria isolated from Omani soil - Hanan S. Al-Hussini; Amna Y. Al-Rawahi; Abdullah A. Al-Marhoon; Shurooq A. Al-Abri; Issa H. Al-Mahmooli; Abdullah M. Al-Sadi; Rethinasamy Velazhahan (Journal of Plant Pathology, 2019)

New pyranosyl cembranoid diterpenes from Sarcophyton trocheliophorum - Mohamed Shaaban; Marwa Y. Issa; Mohamed A. Ghani; Abdelaaty Hamed; Ahmed B. Abdelwahab (Natural Product Research, 2019)

Comparison of the sustainability of bean production systems based on emergy and economic analyses - Mohammad Reza Asgharipour; Hasan Shahgholi; Daniel E. Campbell; Issa Khamari; Adel Ghadiri (Environmental Monitoring and Assessment, 2019)

Comparison of bonobo and chimpanzee brain microstructure reveals differences in socio-emotional circuits - Habon A. Issa; Nicky Staes; Sophia Diggs-Galligan; Cheryl D. Stimpson; Annette Gendron-Fitzpatrick; Jared P. Taglialatela; Patrick R. Hof; William D. Hopkins; Chet C. Sherwood (Brain Structure and Function, 2019)

Effect of recycled glass powder on properties of cementitious materials contains styrene butadiene rubber - Asmahan Issa Jubeh; Doha M. Al Saffar; Bassam A. Tayeh (Arabian Journal of Geosciences, 2019)

Naringenin mitigates titanium dioxide (TiO2)-induced chronic arthritis in mice: role of oxidative stress, cytokines, and NFκB - Marília F. Manchope; Nayara A. Artero; Victor Fattori; Sandra S. Mizokami; Dimitrius L. Pitol; João P. M. Issa; Sandra Y. Fukada; Thiago M. Cunha; José C. Alves-Filho; Fernando Q. Cunha; Rubia Casagrande; Waldiceu A. Verri (Inflammation Research, 2018)

Risk assessment of some organic contaminants: a case study based on food consumption in Tanta and Ismailia cities, Egypt - Asmaa Bayoumi Issa; Khaled Yassin; Naglaa Loutfy; Mohamed Tawfic Ahmed (Environmental Science and Pollution Research, 2018)

Appraisal of interpretation criteria for the single intra-dermal comparative cervical tuberculin test for the diagnosis of tuberculosis in dromedary camels in Ethiopia - Yasmin Jibril; Gezahegne Mamo; Ahmed Issa; Aboma Zewude; Gobena Ameni (Tropical Animal Health and Production, 2018)

Earthquake risk assessment for the building inventory of Muscat, Sultanate of Oman - Ufuk Hancilar; Issa El-Hussain; Karin Sesetyan; Ahmed Deif; Eser Cakti; Ghazi Al-Rawas; Erdal Safak; Khalifa Al-Jabri (Natural Hazards, 2018)

Clinical, Molecular, and Computational Analysis Showed a Novel Homozygous Mutation Among the Substrate-Binding Site of ARSA Protein in Consanguineous Family with Late-Infantile MLD - Abir Ben Issa; Fatma Kammoun Feki; Marwa Ben Jdila; Boudour Khabou; Bochra Ben Rhouma; Leila Ammar-Keskes; Chahnez Triki; Faiza Fakhfakh (Journal of Molecular Neuroscience, 2018)

Genetic variants in components of the NALCN–UNC80–UNC79 ion channel complex cause a broad clinical phenotype (NALCN channelopathies) - Nuria C. Bramswig; Aida M. Bertoli-Avella; Beate Albrecht; Aida I. Al Aqeel; Amal Alhashem; Nouriya Al-Sannaa; Maissa Bah; Katharina Bröhl; Christel Depienne; Nathalie Dorison; Diane Doummar; Nadja Ehmke; et al. (Human Genetics, 2018)

Toxin production by melon root rot fungus, Monosporascus cannonballus - Amna Yaqoob Al-Rawahi; Issa Hashil Al-Mahmooli; Abdullah Mohammed Al-Sadi; Jamal Nasser Al-Sabahi; Rethinasamy Velazhahan (Australasian Plant Pathology, 2018)

Combined acute ecotoxicity of malathion and deltamethrin to Daphnia magna (Crustacea, Cladocera): comparison of different data analysis approaches - Héla Toumi; Moncef Boumaiza; Maurice Millet; Claudemir Marcos Radetski; Baba Issa Camara; Vincent Felten; Jean-François Masfaraud; Jean-François Férard (Environmental Science and Pollution Research, 2018)

Description of risk factors associated with the detection of BVDV antibodies in Brazilian pig herds - Igor Renan Honorato Gatto; Daniel Correia Lima Linhares; Henrique Meiroz de Souza Almeida; Luis Antônio Mathias; Andrea Souza Ramos de Medeiros; Zvonimir Poljak; Samir Issa Samara; Luis Guilherme de Oliveira (Tropical Animal Health and Production, 2018)

Transcription factors network in root endosymbiosis establishment and development - Issa Diédhiou; Diaga Diouf (World Journal of Microbiology and Biotechnology, 2018)

A one-pot synthesis of bis(phenylimino)thiazolidines from ketene N,S-acetals and $${\varvec{N}}$$ N , $${\varvec{N}}'$$ N ′ -diphenyloxalimidoyl dichloride - Issa Yavari; Nooshin Zahedi; Leila Baoosi; Stavroula Skoulika (Molecular Diversity, 2018)

Phylogeographic structure without pre-mating barriers: Do habitat fragmentation and low mobility preserve song and chorus diversity in a European bushcricket? - Mathieu Mahamoud-Issa; Thibaut Marin-Cudraz; Virginie Party; Michael D. Greenfield (Evolutionary Ecology, 2017)

A synthesis of oxo-thioxo[3.3.3]propellanes from dithiocarbamates and ninhydrin–malononitrile adduct - Issa Yavari; Aliyeh Khajeh-Khezri (Molecular Diversity, 2017)

Vocal behaviour of mates at the nest in the White-throated Dipper Cinclus cinclus: contexts and structure of vocal interactions, pair-specific acoustic signature - Avelyne S. Villain; Mathieu Mahamoud-Issa; Blandine Doligez; Clémentine Vignal (Journal of Ornithology, 2017)

A synthesis of functionalized arylthio-acrylates, benzo[b][1,4]thiazines and benzo[4,5]thiazolo[3,2-a]azepines from 2-methylbenzothiazole and acetylenic esters in aqueous media - Issa Yavari; Kiyana Ghafouri; Nooshin Zahedi; Mohammad Reza Halvagar (Molecular Diversity, 2017)

Assessment of the Antibacterial Effect of Chitosan Coated with Heracleum persicum Oil on Rainbow Trout Quality - Issa Mohammadpourfard; Mir Mohammad Shamloo Anbardan; Navid Eshghi; Mahdi Jahanbakhsh; Arash Akbarzadeh; Saeed Ghorbani Bejandi; Mohammad Rezaei (Journal of Aquatic Food Product Technology, 2017)

A synthesis of functionalized dihydro-1H-pyrrolizines and spiropyrrolizines via $$[2+3]$$ [ 2 + 3 ] cycloaddition reactions - Issa Yavari; Leila Baoosi; Mohammad R. Halvagar (Molecular Diversity, 2017)

A synthesis of fused acenaphthopyrrolizines via the 1,3-dipolar cycloaddition reaction of azomethine ylides with acetylenic esters - Issa Yavari; Leila Baoosi; Mohammad R. Halvagar (Molecular Diversity, 2017)

Contributing Causes of Injury or Death in Grain Entrapment, Engulfment, and Extrication - Salah Fuad Issa; William E. Field; Charles V. Schwab; Fadi S. Issa; Eric A. Nauman (Journal of Agromedicine, 2017)

A novel frameshift mutation in the sterol 27-hydroxylase gene in an Egyptian family with cerebrotendinous xanthomatosis without cataract - Mohamed S. Abdel-Hamid; Mahmoud Y. Issa; Ghada A. Otaify; Maha S. Zaki (Metabolic Brain Disease, 2017)

Sedimentology and depositional environments of the Ordovician Umm Sahm Sandstone Formation in southern Jordan - Issa Makhlouf; Abdalla Abu Hamad; Basem Moh’d (Arabian Journal of Geosciences, 2017)

Disaster prevention, disaster preparedness and local community resilience within the context of disaster risk management in Cameroon - Festus Tongwa Aka; Gaston Wung Buh; Wilson Yatoh Fantong; Issa; Isabella Tem Zouh; Serges Laurent Bopda Djomou; Richard Tanwi Ghogomu; Terry Gibson; Mary-Ann Marmol del; Luc Nkamdjou Sigha; Takeshi Ohba; Minoru Kusakabe; et al. (Natural Hazards, 2017)

Iodine-mediated $${ sp}^{3}$$ s p 3 C–H functionalization of methyl ketones: a one-pot synthesis of functionalized indolizines via the 1,3-dipolar cycloaddition reaction between pyridinium ylides and ynones - Issa Yavari; Jamil Sheykhahmadi; Maryam Naeimabadi; Mohammad Reza Halvagar (Molecular Diversity, 2017)

Performance evaluation of HWRF model during post monsoon tropical cyclone Nilofar - Sultan Al-Yahyai; Abeer Aulad Thani; Noura Al-kaabi; Khalifa Al-Sudairi; Badriya Al-Mawali; Issa Al Amri (Arabian Journal of Geosciences, 2017)

In Vitro Comparative Evaluation of Antioxidant Activity of Hydrophobic and Hydrophilic Extracts from Algicolous Fungi - Awatief F. Hifney; Mustafa A. Fawzy; Khayria M. Abdel-Gawad; Ahmed A. Issa; Mohamed Gomaa (Journal of Aquatic Food Product Technology, 2017)

Variation of hydrogeochemical characteristics of water in surface flows, shallow wells, and boreholes in the coastal city of Douala (Cameroon) - Wilson Y. Fantong; Brice T. Kamtchueng; Beatrice Ketchemen-Tandia; Doris Kuitcha; Josephine Ndjama; Alain T. Fouepe; Gloria E. Takem; Issa; Mengnjo J. Wirmvem; Serges L. Bopda Djomou; Andrew A. Ako; George E. Nkeng; et al. (Hydrological Sciences Journal, 2016)

Intraseasonal variability of low-level moisture transport over West Africa - M. Issa Lélé; Lance M. Leslie (Climate Dynamics, 2016)

Lead line in rodents: an old sign of lead intoxication turned into a new method for environmental surveillance - Fellipe Augusto Tocchini de Figueiredo; Junia Ramos; Erika R. Hashimoto Kawakita; Alina S. Bilal; Frederico B. de Sousa; William D. Swaim; Joao P. Mardegan Issa; Raquel F. Gerlach (Environmental Science and Pollution Research, 2016)

Influence of size of granulated rubber on bearing capacity of fine-grained sand - Seyed Mahmoud Anvari; Issa Shooshpasha (Arabian Journal of Geosciences, 2016)

A Computational Framework for Personalized Blood Flow Analysis in the Human Left Atrium - Tomohiro Otani; Abdullah Al-Issa; Amir Pourmorteza; Elliot R. McVeigh; Shigeo Wada; Hiroshi Ashikaga (Annals of Biomedical Engineering, 2016)

Probabilistic tsunami hazard assessment along Oman coast from submarine earthquakes in the Makran subduction zone - Issa El-Hussain; Rachid Omira; Ahmed Deif; Zaid Al-Habsi; Ghazi Al-Rawas; Adel Mohamad; Khalifa Al-Jabri; Maria Ana Baptista (Arabian Journal of Geosciences, 2016)

Mapping stakeholder viewpoints in biodiversity management: an application in Niger using Q methodology - Issa Hamadou; Nassim Moula; Seyni Siddo; Moumouni Issa; Hamani Marichatou; Pascal Leroy; Nicolas Antoine-Moussiaux (Biodiversity and Conservation, 2016)

Inhibition of p90 ribosomal S6 kinase attenuates cell migration and proliferation of the human lung adenocarcinoma through phospho-GSK-3β and osteopontin - Nabeel Abdulrahman; Maiy Jaballah; Noufira Poomakkoth; Sadaf Riaz; Somaia Abdelaziz; Aya Issa; Fatima Mraiche (Molecular and Cellular Biochemistry, 2016)

Development of ground-shaking maps for the Sultanate of Oman - Eser Çaktı; Issa El-Hussain; Karin Şeşetyan; Ahmed Deif; Ufuk Hancılar; Ghazi Al-Rawas; Yaver Kamer; Khalifa Al-Jabri (Natural Hazards, 2016)

Thermal maturity and hydrocarbon generation of the Dawi Formation, Belayim Marine Oil Field, Gulf Of Suez, Egypt: a 1D Basin Modeling Case Study - Mohamed Moustafa Afife; Mohamed Abu Al-Atta; Mohammed A. Ahmed; Ghalib Ibrahim Issa (Arabian Journal of Geosciences, 2016)

A 3-year long study of Staphylococcus aureus isolates from subclinical mastitis in three Azawak zebu herds at the Sahelian experimental farm of Toukounous, Niger - Abdoulkarim Ibrahim Issa; Jean-Noël Duprez; Rianatou Bada-Alambedji; Mamane Djika; Jacques Georges Mainil; Marjorie Bardiau (Tropical Animal Health and Production, 2016)

Pulmonary capillary reserve and exercise capacity at high altitude in healthy humans - Bryan J. Taylor; Kirsten E. Coffman; Douglas T. Summerfield; Amine N. Issa; Alex J. Kasak; Bruce D. Johnson (European Journal of Applied Physiology, 2016)

Biodegradation of Palisada perforata (Rhodophyceae) and Sargassum sp. (Phaeophyceae) biomass by crude enzyme preparations from algicolous fungi - Mohamed Gomaa; Awatief F. Hifney; Mustafa A. Fawzy; Ahmed A. Issa; Khayria M. Abdel-Gawad (Journal of Applied Phycology, 2015)

Identification of quantitative trait loci for yield and yield related traits in groundnut (Arachis hypogaea L.) under different water regimes in Niger and Senegal - Issa Faye; Manish K. Pandey; Falalou Hamidou; Abhishek Rathore; Ousmane Ndoye; Vincent Vadez; Rajeev K. Varshney (Euphytica, 2015)
Yield under drought stress is a highly complex trait with large influence to even a minor fluctuation in the environmental conditions. Genomics-assisted breeding holds great promise for improving such complex traits more efficiently in less time, but requires markers associated with the trait of interest. In this context, a recombinant inbred line mapping population (TAG 24 × ICGV 86031) was used to identify markers associated with quantitative trait loci (QTLs) for yield and yield related traits at two important locations of West Africa under well watered and water stress conditions. Among the traits analyzed under WS condition, the harvest index (HI) and the haulm yield (HYLD) were positively correlated with the pod yield (PYLD) and showed intermediate broad sense heritability. QTL analysis using phenotyping and genotyping data resulted in identification of 52 QTLs. These QTLs had low phenotypic variance (<12 %) for all the nine traits namely plant height, primary branching, SPAD chlorophyll meter reading, percentage of sound mature kernels, 100 kernel weight, shelling percentage, HI, HYLD and PYLD. Interestingly, few QTLs identified in this study were also overlapped with previously reported QTLs detected for drought tolerance related traits identified earlier in Indian environmental conditions using the same mapping population. Accumulating these many small-effect QTLs into a single genetic background is nearly impossible through marker-assisted backcrossing and even marker-assisted recurrent selection. Under such circumstances, the deployment of genomic selection is the most appropriate approach for improving such complex traits with more precision and in less time.

A direct access to heptasubstituted biguanides - Issa Yavari; Manijeh Nematpour (Molecular Diversity, 2015)

An echographic study of follicular growth during induced estrus in female Azawak zebu in Niger - Mahamadou Moussa Garba; Moumouni Issa; Hamani Marichatou; Christian Hanzen (Tropical Animal Health and Production, 2015)

Cytotoxic flavonoids and other constituents from the stem bark of Ochna schweinfurthiana - Joseph T. Ndongo; Mark E. Issa; Angelique N. Messi; Joséphine Ngo Mbing; Muriel Cuendet; Dieudonné E. Pegnyemb; Christian G. Bochet (Natural Product Research, 2015)

CYP2B6 rs2279343 polymorphism is associated with smoking cessation success in bupropion therapy - Paulo Roberto Xavier Tomaz; Juliana Rocha Santos; Jaqueline Scholz Issa; Tânia Ogawa Abe; Patrícia Viviane Gaya; José Eduardo Krieger; Alexandre Costa Pereira; Paulo Caleb Júnior Lima Santos (European Journal of Clinical Pharmacology, 2015)

Absolute gravity measurements by using FG5 and A10 absolute gravimeters in the Kingdom of Saudi Arabia - Mehmet Emin Ayhan; Bandar Saleh Abdulkareem Al-Muslmani; Jeff Kanney; Othman Abdulmohsen Issa Al-Kherayef (Arabian Journal of Geosciences, 2015)

Response of Quinoa to Different Water Management Strategies: Field Experiments and Saltmed Model Application Results - Rachid Fghire; Said Wahbi; Fatima Anaya; Oudou Issa Ali; Ouafae Benlhabib; Ragab Ragab (Irrigation and Drainage, 2015)
Given the current water shortage in North Africa, improving water management to produce more crop per drop is vital. In addition, the introduction of drought‐tolerant, less water‐consuming crops such as quinoa is of great interest. To understand the response of quinoa to water stress in terms of biomass and grain yield under various irrigation management strategies, the SALTMED model was employed using field measurements during the cropping seasons of 2011 and 2012 at a site in the Marrakech region, south Morocco. Quinoa showed its ability to grow in the south of Morocco and give a good yield under full irrigation. However, the experimental and modelling results showed that under rainfed and deficit irrigation, the grain yield was lower than under the full irrigation treatment and was dependent on water deficit level. The study revealed that a reasonable grain yield of quinoa can only be obtained if it was subjected to moderate water stress conditions. The results indicated that the SALTMED model is able to simulate the quinoa biomass and grain yield under various water deficit levels and that the model can be used in the evaluation of different irrigation strategies. Copyright © 2015 John Wiley & Sons, Ltd.

A tandem synthesis of 5-sulfonylimino-2-imidazolones from sulfonoketenimides and dialkyl azodicarboxylates - Issa Yavari; Manijeh Nematpour; Ehsan Ghanbari (Molecular Diversity, 2014)

Spatio-temporal, environmental factors, and host identity shape culturable-epibiotic fungi of seaweeds in the Red Sea, Egypt - Khayria M. Abdel-Gawad; Awatief F. Hifney; Ahmed A. Issa; Mohamed Gomaa (Hydrobiologia, 2014)

Evaluation of molecular markers for the diagnosis of Mycobacterium bovis - Mariana Lázaro Sales; Antônio Augusto Fonseca; Érica Bravo Sales; Ana Cláudia Pinto Cottorello; Marina Azevedo Issa; Mikael Arrais Hodon; Paulo Martins Soares Filho; Alberto Knust Ramalho; Marcio Roberto Silva; Andrey Pereira Lage; Marcos Bryan Heinemann (Folia Microbiologica, 2014)

Quantifying the response of free-ranging mammalian herbivores to the interplay between plant defense and nutrient concentrations - Miguel A. Bedoya-Pérez; Daniel D. Issa; Peter B. Banks; Clare McArthur (Oecologia, 2014)

Analysing the relationship between land units and plant communities: The case of Socotra Island (Yemen) - F. Attorre; A. Issa; L. Malatesta; A. Adeeb; M. De Sanctis; M. Vitale; A. Farcomeni (Plant Biosystems, 2014)

Accumulation of phlorotannins in the abalone Haliotis discus hannai after feeding the brown seaweed Ecklonia cava - Issa Bangoura; Muhammad Tanvir Hossain Chowdhury; Ji-Young Kang; Ji-Young Cho; Je-Cheon Jun; Yong-Ki Hong (Journal of Applied Phycology, 2014)

The effects of surcharge on liquefaction resistance of silty sand - Issa Shooshpasha; Mohsen Bagheri (Arabian Journal of Geosciences, 2014)

Lumpy skin disease of cattle: an emerging problem in the Sultanate of Oman - Mohamed Hassan Tageldin; David Brian Wallace; Gertruida Hermanna Gerdes; John Fraser Putterill; Roelf Rudolph Greyling; Maanda Noaxe Phosiwa; Rashied Mohammed Al Busaidy; Sultan Issa Al Ismaaily (Tropical Animal Health and Production, 2014)

Sulfonoketenimides as key intermediates for the synthesis of 2-thioxo-2 $$H$$ H -1,3-thiazines and 2-arylimino-2 $$H$$ H -1,3-thiazines - Issa Yavari; Manijeh Nematpour; Tahereh Damghani (Molecular Diversity, 2013)

A tandem synthesis of functionalized azet-2 $$(1H)$$ ( 1 H ) -ones and azet-2 $$(1H)$$ ( 1 H ) -thiones - Issa Yavari; Manijeh Nematpour; Mohammad J. Bayat (Molecular Diversity, 2013)

Sedimentation and new operational curves for Mosul Dam, Iraq - Issa E. Issa; Nadhir Al-Ansari; Sven Knutsson (Hydrological Sciences Journal, 2013)

Susceptibility gene search for nephropathy and related traits in Mexican–Americans - Farook Thameem; Issa A. Kawalit; Sharon G. Adler; Hanna E. Abboud (Molecular Biology Reports, 2013)

Modulation of cytochrome P450 1 (Cyp1) by vanadium in hepatic tissue and isolated hepatocyte of C57BL/6 mice - Ghada Abdelhamid; Issa E. A. Amara; Anwar Anwar-Mohamed; Ayman O. S. El-Kadi (Archives of Toxicology, 2013)

Inhibition of pancreatic lipase by berberine and dihydroberberine: an investigation by docking simulation and experimental validation - Mohammad Mohammad; Ihab M. Al-masri; Ala Issa; Ayman Khdair; Yasser Bustanji (Medicinal Chemistry Research, 2013)

The contribution of shallow groundwater by safflower (Carthamus tinctorius L.) under high water table conditions, with and without supplementary irrigation - Houshang Ghamarnia; Mohsen Golamian; Saloome Sepehri; Issa Arji; Samera Norozpour (Irrigation Science, 2013)

Stability and equation of state of post-aragonite BaCO3 - Joshua P. Townsend; Yun-Yuan Chang; Xiaoting Lou; Miguel Merino; Scott J. Kirklin; Jeff W. Doak; Ahmed Issa; Chris Wolverton; Sergey N. Tkachev; Przemyslaw Dera; Steven D. Jacobsen (Physics and Chemistry of Minerals, 2013)

Tandem synthesis of highly functionalized pyrazole derivatives from terminal alkynes, sulfonyl azides, diethyl azadicarboxylate, and sodium arylsulfinates - Issa Yavari; Manijeh Nematpour (Molecular Diversity, 2012)

Differential modulation of aryl hydrocarbon receptor regulated enzymes by arsenite in the kidney, lung, and heart of C57BL/6 mice - Anwar Anwar-Mohamed; Ghada Abdelhamid; Issa E. A. Amara; Ayman O. S. El-Kadi (Archives of Toxicology, 2012)

Multiple source imagery and linear features for detection of urban expansion in Aqaba City, Jordan - Rami Issa Al-Ruzouq; Abdallah Al-Zoubi; Emad E. Akawi; Abdalrahman A. Abueladas; Tina M. Niemi (International Journal of Remote Sensing, 2012)

Bacterial diversity of periodontal and implant-related sites detected by the DNA Checkerboard method - C. Nascimento; N. Monesi; I. Y. Ito; J. P. M. Issa; R. F. Albuquerque Junior (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Adaptive evolution of a key gene affecting queen and worker traits in the honey bee, Apis mellifera - CLEMENT F. KENT; AMER ISSA; ALEXANDRA C. BUNTING; AMRO ZAYED (Molecular Ecology, 2011)
The vitellogenin egg yolk precursor protein represents a well‐studied case of social pleiotropy in the model organism Apis mellifera . Vitellogenin is associated with fecundity in queens and plays a major role in controlling division of labour in workers, thereby affecting both individual and colony‐level fitness. We studied the molecular evolution of vitellogenin and seven other genes sequenced in a large population panel of Apis mellifera and several closely related species to investigate the role of social pleiotropy on adaptive protein evolution. We found a significant excess of nonsynonymous fixed differences between A. mellifera , A. cerana and A. florea relative to synonymous sites indicating high rates of adaptive evolution at vitellogenin. Indeed, 88% of amino acid changes were fixed by selection in some portions of the gene. Further, vitellogenin exhibited hallmark signatures of selective sweeps in A. mellifera , including a significant skew in the allele frequency spectrum, extreme levels of genetic differentiation and linkage disequilibrium. Finally, replacement polymorphisms in vitellogenin were significantly enriched in parts of the protein involved in binding lipid, establishing a link between the gene’s structure, function and effects on fitness. Our case study provides unequivocal evidence of historical and ongoing bouts of adaptive evolution acting on a key socially pleiotropic gene in the honey bee.

Neurologic and ocular phenotype in Pitt–Hopkins syndrome and a zebrafish model - Antje Brockschmidt; Alida Filippi; Peter Charbel Issa; Michael Nelles; Horst Urbach; Nicole Eter; Wolfgang Driever; Ruthild G. Weber (Human Genetics, 2011)

Systematic and random transitions of land-cover types in Burkina Faso, West Africa - Issa Ouedraogo; Patrice Savadogo; Mulualem Tigabu; Sidzabda Djibril Dayamba; Per Christer Odén (International Journal of Remote Sensing, 2011)

WEPP and ANN models for simulating soil loss and runoff in a semi-arid Mediterranean region - Issa Albaradeyia; Azzedine Hani; Isam Shahrour (Environmental Monitoring and Assessment, 2011)

Domino Michael–O-alkylation: one-pot synthesis of dialkyl 4-oxo-2,3-dihydro-2,3-furandicarboxylates - Issa Yavari; Mehdi Sirouspour; Sanaz Souri (Molecular Diversity, 2011)

Synthesis of new series of pyrazolo[4,3-d]pyrimidin-7-ones and pyrido[2,3-d]pyrimidin-4-ones for their bacterial and cyclin-dependent kinases (CDKs) inhibitory activities - Detlef Geffken; Raafat Soliman; Farid S. G. Soliman; Magdi M. Abdel-Khalek; Doaa A. E. Issa (Medicinal Chemistry Research, 2011)

Shallow groundwater use by Safflower (Carthamus tinctorius L.) in a semi-arid region - Houshang Ghamarnia; Mohsen Golamian; Saloome Sepehri; Issa Arji (Irrigation Science, 2011)

Resistance mechanism to the pod-sucking bug Clavigralla tomentosicollis (Hemiptera: Coreidae) in the cowpea IT86D-716 variety - Clementine L. Dabire-Binso; Niango Malick Ba; Antoine Sanon; Issa Drabo; Kouahou Foua Bi (International Journal of Tropical Insect Science, 2010)

Extraction of Co, Ni, Cu, Zn and Cd ions using 2-aminophenylaminopropylpolysiloxane - Nizam M. El-Ashgar; Issa M. El-Nahhal; Mohamed M. Chehimi; Florence Babonneau; Jacques Livage (Environmental Chemistry Letters, 2010)

Synthesis of functionalized 1,2,4-triazole-3-thiones from ammonium isothiocyanate, acid chlorides, and arylhydrazines - Issa Yavari; Faezeh Shirgahi-Talari; Zinatossadat Hossaini; Maryam Sabbaghan; Samereh Seyfi (Molecular Diversity, 2010)

A synthesis of phosphorylated dioxohexahydropyrimidines from N,N′-dimethylurea, activated acetylenes, and trialkyl phosphites - Issa Yavari; Manijeh Nematpour; Zinatossadat Hossaini (Molecular Diversity, 2010)

Boronated phosphonium salts containing arylboronic acid, closo-carborane, or nido-carborane: synthesis, X-ray diffraction, in vitro cytotoxicity, and cellular uptake - Daniel E. Morrison; Fatiah Issa; Mohan Bhadbhade; Ludwig Groebler; Paul K. Witting; Michael Kassiou; Peter J. Rutledge; Louis M. Rendina (JBIC Journal of Biological Inorganic Chemistry, 2010)

Data fusion of multi-source imagery based on linear features registration - Rami Issa Al-Ruzouq (International Journal of Remote Sensing, 2010)

Rate of seawater intrusion estimated by geophysical methods in an arid area: Al Khabourah, Oman - Osman A. E. Abdalla; Mubarik Ali; Khalifa Al-Higgi; Hilal Al-Zidi; Issa El-Hussain; Said Al-Hinai (Hydrogeology Journal, 2010)

One-pot synthesis of functionalized 4-oxo-2-thioxo-1,3-thiazinanes from primary amines, CS2, and itaconic anhydride - Issa Yavari; Mehdi Sirouspour; Sanaz Souri (Molecular Diversity, 2010)

Diastereoselective synthesis of fused [1,3]oxazines from ethyl pyruvate, activated acetylenes and N-heterocycles - Issa Yavari; Anvar Mirzaei; Zinatosadat Hossaini; Sanaz Souri (Molecular Diversity, 2010)

Efficient and green synthesis of tetrasubstituted pyrroles promoted by task-specific basic ionic liquids as catalyst in aqueous media - Issa Yavari; Elaheh Kowsari (Molecular Diversity, 2009)

Diastereoselective synthesis of fused [1,3]thiazolo[1,3]oxazins and [1,3]oxazino[2,3-b][1,3]benzothiazoles - Issa Yavari; Zinatossadat Hossaini; Sanaz Souri; Samereh Seyfi (Molecular Diversity, 2009)

A one-pot synthesis of functionalized thiazoles from acid chlorides, secondary amines, ethyl bromopyruvate, and ammonium thiocyanate - Issa Yavari; Zinatossadat Hossaini; Maryam Sabbaghan; Majid Ghazanfarpour-Darjani (Molecular Diversity, 2009)

Nostoc cyanobacterial inoculation in South African agricultural soils enhances soil structure, fertility, and maize growth - M. P. Maqubela; P. N. S. Mnkeni; O. Malam Issa; M. T. Pardo; L. P. D’Acqui (Plant and Soil, 2009)

Enhanced L1CAM expression on pancreatic tumor endothelium mediates selective tumor cell transmigration - Yasmin Issa; Daniel Nummer; Tobias Seibel; Susanne Sebens Müerköster; Moritz Koch; Friedrich-Hubertus Schmitz-Winnenthal; Luis Galindo; Juergen Weitz; Philipp Beckhove; Peter Altevogt (Journal of Molecular Medicine, 2009)

Hormone receptor-related gene polymorphisms and prostate cancer risk in North Indian population - Khadijeh Onsory; R. C. Sobti; Adnan Issa Al-Badran; Masatoshi Watanabe; Taizo Shiraishi; Awtar Krishan; Harsh Mohan; Pushpinder Kaur (Molecular and Cellular Biochemistry, 2008)

Parasite Prevalence, Abundance, and Diversity in a Semi-free-ranging Colony of Mandrillus sphinx - Joanna M. Setchell; Issa-Ben Bedjabaga; Benoit Goossens; Patricia Reed; E. Jean Wickings; Leslie A. Knapp (International Journal of Primatology, 2007)

Involvement of PPAR-γ and p53 in DHA-induced apoptosis in Reh cells - Hamid Zand; Ali Rhimipour; Masoomeh Bakhshayesh; Mohammad Shafiee; Issa Nour Mohammadi; Saideh Salimi (Molecular and Cellular Biochemistry, 2007)

Efficient synthesis of alkyl 2-[2-(arylcarbonylimino)-3-aryl-4-oxo-1, 3-thiazolan-5-ylidene]-acetates - Issa Yavari; Maryam Sabbaghan; Khalil Porshamsian; Mohammad Bagheri; Safa Ali-Asgari; Zinatossadat Hossaini (Molecular Diversity, 2007)

Making a friend from a foe: expressing a GroEL gene from the whitefly Bemisia tabaci in the phloem of tomato plants confers resistance to tomato yellow leaf curl virus - F. Akad; A. Eybishtz; D. Edelbaum; R. Gorovits; O. Dar-Issa; N. Iraki; H. Czosnek (Archives of Virology, 2007)

A novel gene for Usher syndrome type 2: mutations in the long isoform of whirlin are associated with retinitis pigmentosa and sensorineural hearing loss - Inga Ebermann; Hendrik P. N. Scholl; Peter Charbel Issa; Elvir Becirovic; Jürgen Lamprecht; Bernhard Jurklies; José M. Millán; Elena Aller; Diana Mitter; Hanno Bolz (Human Genetics, 2007)

Reaction between alkyl isocyanides and isopropylidene Meldrum’s acid in the presence of bidentate nucleophiles - Issa Yavari; Maryam Sabbaghan; Zinatossadat Hossaini (Molecular Diversity, 2007)

Effects of the inoculation of cyanobacteria on the microstructure and the structural stability of a tropical soil - Oumarou Malam Issa; Christian Défarge; Yves Le Bissonnais; Béatrice Marin; Odile Duval; Ary Bruand; Luigi Paolo D’Acqui; Sofie Nordenberg; Marcus Annerman (Plant and Soil, 2007)

Secondary sexual characters and female quality in primates - Joanna M. Setchell; Marie J. E. Charpentier; Issa-Ben Bedjabaga; Patricia Reed; E. Jean Wickings; Leslie A. Knapp (Behavioral Ecology and Sociobiology, 2006)

Identification and characterization of microsatellites for striped bass from repeat-enriched libraries - Caird Rexroad; Roger Vallejo; Issa Coulibaly; Charlene Couch; Amber Garber; Mark Westerman; Craig Sullivan (Conservation Genetics, 2006)

Synthesis of functionalized 5-imino-2,5-dihydro-furans through the reaction of isocyanides with activated acetylenes in the presence of ethyl bromopyruvate - Issa Yavari; Zinatossadat Hossaini; Maryam Sabbaghan (Molecular Diversity, 2006)

Three-component synthesis of functionalized 5-oxo-4,5-dihydroindeno[1,2-b]pyrans - Issa Yavari; Mehdi Sirouspour; Sanaz Souri (Molecular Diversity, 2006)

Three-Component Synthesis of Dialkyl 2-(Alkylimino-Methylene)3- (2,2,5-Trimethyl-4,6-Dioxo-1,3-Dioxan-5-Yl)-Succinates - Issa Yavari; Hasan Zare; Bita Mohtat (Molecular Diversity, 2006)

Parasitic Nematodes in the Chimpanzee Population on Rubondo Island, Tanzania - Klara J. Petrzelkova; Hideo Hasegawa; Liza R. Moscovice; Taranjit Kaur; Mwanahamissi Issa; Michael A. Huffman (International Journal of Primatology, 2006)

Three-component reaction between triphenylphosphine, dialkyl acetylenedicarboxylates and urea or N-methylurea - Issa Yavari; Nader Zabarjad-Shiraz (Molecular Diversity, 2006)

Ovarian tissue cryopreservation: benefits and risks - Murat Sonmezer; Mousa Issa Shamonki; Kutluk Oktay (Cell and Tissue Research, 2005)

Expression of Basic Fibroblast Growth Factor mRNA and Protein in the Human Brain following Ischaemic Stroke - Razao Issa; Ahmed AlQteishat; Nick Mitsios; Mohamad Saka; Jerzy Krupinski; Elizabeth Tarkowski; John Gaffney; Mark Slevin; Shant Kumar; Pat Kumar (Angiogenesis, 2005)

Artificial Insemination Using Local Cattle Breeds in Niger - F. Cristofori; M. Issa; A. Yenikoye; G. Trucchi; G. Quaranta; M. Chanono; C. Semita; H. Marichatou; M. Mattoni (Tropical Animal Health and Production, 2005)

Synthesis of dialkyl 2,5-dihydro-5-oxo-1,2-azaphosphole-3,4-dicarboxylates - Issa Yavari; Abdolali Alizadeh; Mohammad Anary-Abbasinejad (Molecular Diversity, 2005)

A simple approach to the synthesis of highly functionalized pyrrole derivatives - Issa Yavari; Mohammad Anary-Abbasinejad; Farough Nasiri; Hoorieh Djahaniani; Abdolali Alizadeh; Hamid R. Bijanzadeh (Molecular Diversity, 2005)

Synthesis and dynamic NMR study of ketenimines derived from tert-butyl isocyanide, alkyl 2-arylamino-2-oxo-acetates, and dialkyl acetylenedicarboxylates - Issa Yavari; Farough Nasiri; Horieh Djahaniani (Molecular Diversity, 2004)

The influence of the sterilisation process on certain thermal properties - Manal Issa; Maria Jose Abreu; Laurence Schacher; Dominique Adolphe; Maria Elisabete Cabeco Silva (European Journal of Applied Physiology, 2004)

Epigenetic changes in colorectal cancer - Yutaka Kondo; Jean-Pierre J. Issa (Cancer and Metastasis Reviews, 2004)

A methodological study on participatory barley breeding II. Response to selection - S. Ceccarelli; S. Grando; M. Singh; M. Michael; A. Shikho; M. Al Issa; A. Al Saleh; G. Kaleonjy; S.M. Al Ghanem; A.L. Al Hasan; H. Dalla; S. Basha; et al. (Euphytica, 2003)

Molecular identification of Salmonella isolates from poultry and meat productsin Irbid City, Jordan - Hanan Issa Malkawi (World Journal of Microbiology and Biotechnology, 2003)

Implications of density correction in gravimetric method for water flux determination using rat single-pass intestinal perfusion technique: A technical note - Chayapathy Issa; Piyush Gupta; Arvind K. Bansal (AAPS PharmSciTech, 2003)

Efficacite du Triflumuron Selon la Nature et la Couleur du Tissu a L'egard de Glossina palpalis gambiensis Vanderplank, 1949 - Augustin Ziro Bance; Albert Patoin Ouedraogo; Burkhard Bauer; Idrissa Kabore; et Issa Sidibe (International Journal of Tropical Insect Science, 2002)

Proline alleviates heavy metal stress inScenedesmus armatus - A. E. El-Enany; A. A. Issa (Folia Microbiologica, 2001)

Effect of manganese and calcium deficiency on the growth and oxygen exchange ofScenedesmus intermedius cultured for successive generations - M. S. Adam; A. A. Issa (Folia Microbiologica, 2000)

Notes on the Ecology of a Natural Glossina austeni (Diptera: Glossinidae) Population in the Jozani Forest, Unguja Island of Zanzibar - Marc J. B. Vreysen; Issa S. Khamis (International Journal of Tropical Insect Science, 1999)

Influence of selenium on toxicity of some heavy metals in the green algaScenedesmus obliquus - A. A. Issa; M. S. Adam (Folia Microbiologica, 1999)

An Evaluation of Insecticide-Impregnated Screens against Glossina Austeni (Diptera: Glossinidae) on Unguja Island of Zanzibar - Marc J. B. Vreysen; Khalfan M. Saleh; Issa S. Khamis; Furaha Mramba (International Journal of Tropical Insect Science, 1999)

Molecular mechanism of vitamin D receptor action - L. L. Issa; G. M. Leong; J. A. Eisman (Inflammation Research, 1998)

Effect of Ca2+ on the detoxification of Cd2+ byScenedesmus obliquus cells at low or high temperature - A. A. Issa; M. S. Adam; R. Abdel-Basset (Folia Microbiologica, 1998)

Mapping of the ribonucleotide reductase genes (Rrm1, Rrm2) in the rat - K. Klinga-Levan; K. Helou; R. Issa; C. Szpirer; J. Szpirer; G. Levan (Mammalian Genome, 1997)